Resin composition, photosensitive film, photosensitive film with support, printed wiring board, and semiconductor device
By using a resin composition containing a naphthalene frame resin and an inorganic filler material, the problem of insufficient lateral corrosion resistance of the solder resist layer in the prior art is solved, and the shape of the opening part and the improvement of welding adhesion during the welding process is achieved.
Patent Information
- Application Number
- CN202411912666.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2018-09-27
- Filing Date
- 2019-09-26
- Publication Date
- 2025-03-14
AI Technical Summary
It is difficult to obtain cured substances with excellent lateral corrosion resistance in the prior art, especially during solder welding, the cross-sectional shape of the opening part of the solder resist layer is prone to form an inverted cone shape, which affects the welding adhesion.
A resin composition containing (A) a resin containing ethylenically unsaturated groups and carboxyl groups, (B) an inorganic filler material with an average particle size of 0.5 μm or more, (C) an epoxy resin, and (D) a photopolymerization initiator are used, wherein the component (A) contains (A-1) a resin containing a naphthalene skeleton, and the dissolution rate in the alkaline solution meets a specific range.
A cured product with excellent lateral corrosion resistance is achieved, ensuring that the sides of the opening part are close to perpendicular to the layer plane during welding, and improving welding adhesion and quality of the insulating layer.
Smart Images

Figure BDA0005206112370000051 
Figure BDA0005206112370000061 
Figure BDA0005206112370000062
Abstract
Description
This application is a divisional application of the Chinese patent application with application number 201910916685.7, application date September 26, 2019, and invention name “Resin composition, photosensitive film, photosensitive film with support, printed wiring board and semiconductor device”. Technical Field
[0001] The present invention relates to a resin composition and also to a photosensitive film, a photosensitive film with a support, a printed wiring board, and a semiconductor device obtained by using the resin composition. Background Art
[0002] In a printed wiring board, a solder resist layer is sometimes provided as a permanent protective film for preventing solder from adhering to a portion where solder is not required and preventing corrosion of the circuit board. As the solder resist layer, a photosensitive resin composition such as that described in Patent Document 1 is generally used.
[0003] Prior art literature Patent Literature Patent Document 1: Japanese Patent Application Publication No. 2014-115672 Summary of the invention
[0004] Problems to be solved by the invention In order to connect the substrates by soldering, the solder mask is required to have a fine opening pattern that exposes a part of the conductor layer with the wiring pattern. In addition, from the perspective of the adhesion of the solder, it is required that the cross-sectional shape of the opening cannot be formed into an inverted cone, and the side of the opening is particularly required to be close to vertical relative to the layer plane. Here, the cross-sectional shape of the inverted cone refers to the shape that the diameter of the opening is wider and wider toward the inside, specifically, refers to the shape that the bottom surface of the opening is wider than the top surface of the opening. In this specification, sometimes such a cross-sectional shape is not easy to be formed into an inverted cone and is referred to as "anti-side erosion (undercut) property" excellent. It should be noted that the above-mentioned topic is a topic that is also generated outside the situation of using a resin composition to form a solder mask.
[0005] An object of the present invention is to provide a resin composition capable of obtaining a cured product having excellent side etching resistance; and a photosensitive film, a photosensitive film with a support, a printed wiring board, and a semiconductor device obtained by using the resin composition.
[0006] Solutions to Solve Problems The present inventors have conducted intensive studies to solve the above-mentioned problems and have found that the above-mentioned problems can be solved by using a resin composition comprising (A) a resin containing an ethylenically unsaturated group and a carboxyl group, (B) an inorganic filler having an average particle size of 0.5 μm or more, (C) an epoxy resin, and (D) a photopolymerization initiator, wherein component (A) contains (A-1) a resin containing a naphthalene skeleton, thereby completing the present invention.
[0007] Furthermore, the present inventors have conducted intensive studies to solve the above-mentioned problems, and have found that by using a resin composition containing (A) a resin containing an ethylenically unsaturated group and a carboxyl group, (B) an inorganic filler having an average particle size of 0.5 μm or more, (C) an epoxy resin, and (D) a photopolymerization initiator, the weighted average S of the dissolution rate [nm / sec] of the component (A) in an alkaline solution based on the mass ratio is 1:1. (A) The above-mentioned problems can be solved by satisfying the following formula (I), thereby completing the present invention; 5≤S (A) ≤110···(I).
[0008] That is, the present invention includes the following contents; [1] A resin composition comprising the following components: (A) a resin containing an ethylenically unsaturated group and a carboxyl group, (B) an inorganic filler having an average particle size of 0.5 μm or more, (C) epoxy resin, and (D) a photopolymerization initiator, The component (A) contains: (A-1) a resin having a naphthalene skeleton. [2] The resin composition according to [1], wherein the component (A-1) is a naphthol aralkyl type resin. [3] The resin composition according to [1] or [2], wherein the content of the component (A-1) is 5% by mass or more when the nonvolatile component in the component (A) is 100% by mass. [4] The resin composition according to any one of [1] to [3], wherein the content of the component (A) is 10% by mass or more and 30% by mass or less, based on 100% by mass of a nonvolatile component in the resin composition. [5] The resin composition according to any one of [1] to [4], wherein the content of the component (B) is 60% by mass or more when the nonvolatile component in the resin composition is 100% by mass. [6] The resin composition according to any one of [1] to [5], wherein the component (A) contains: (A-2) Acid-modified epoxy (meth)acrylate resin other than the component (A-1). [7] The resin composition according to any one of [1] to [6], wherein (A) Weighted average S of the dissolution rate [nm / sec] of the component in the alkaline solution based on the mass ratio (A) Satisfies the following formula (I): 5≤S(A) ≤110···(I). [8] A resin composition comprising the following components: (A) a resin containing an ethylenically unsaturated group and a carboxyl group, (B) an inorganic filler having an average particle size of 0.5 μm or more, (C) epoxy resin, and (D) a photopolymerization initiator, wherein the weighted average S of the dissolution rate [nm / sec] of the component (A) in an alkaline solution based on the mass ratio is (A) Satisfies the following formula (I): 5≤S (A) ≤110···(I). [9] The resin composition according to any one of [1] to [8], which is a resin composition for forming a solder resist layer of a printed wiring board.
[10] A photosensitive film comprising the resin composition according to any one of [1] to [9].
[11] A photosensitive film with a support, comprising: a support; and a resin composition layer comprising the resin composition according to any one of [1] to [9], provided on the support.
[12] A printed wiring board comprising an insulating layer formed from a cured product of the resin composition according to any one of [1] to [9].
[13] A semiconductor device comprising the printed wiring board described in
[12] .
[0009] Effects of the Invention According to the present invention, there are provided a resin composition capable of obtaining a cured product having excellent side etching resistance; and a photosensitive film, a photosensitive film with a support, a printed wiring board, and a semiconductor device obtained by using the resin composition. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 1 is a cross-sectional view of a laminate for evaluation used in Examples of the present invention, schematically showing a state when cut along a plane passing through the central axis of a circular through hole formed in an insulating layer. DETAILED DESCRIPTION
[0011] [1. Resin composition according to first embodiment of the present invention] Hereinafter, the resin composition according to the first embodiment of the present invention will be described in detail.
[0012] The resin composition of the first embodiment of the present invention is a resin composition containing (A) a resin containing an ethylenically unsaturated group and a carboxyl group, (B) an inorganic filler having an average particle size of 0.5 μm or more, (C) an epoxy resin, and (D) a photopolymerization initiator. The (A) component of the resin composition of the first embodiment contains (A-1) a resin containing a naphthalene skeleton. By using the resin composition of the first embodiment of the present invention, a cured product having excellent side erosion resistance can be obtained.
[0013] The resin composition may further contain (E) a reactive diluent, (F) an organic solvent, and (G) other additives as necessary. Hereinafter, each component contained in the resin composition will be described in detail.
[0014] <(A) Resin containing an ethylenically unsaturated group and a carboxyl group> The resin composition contains (A) a resin containing an ethylenically unsaturated group and a carboxyl group.
[0015] As the ethylenically unsaturated group, for example, vinyl, allyl, propargyl, butenyl, ethynyl, phenylethynyl, maleimide, nadiimide, (meth)acryloyl, from the viewpoint of the reactivity of photo-radical polymerization, preferably (meth)acryloyl. The so-called "(meth)acryloyl" includes methacryloyl, acryloyl and a combination thereof. Since the (A) component contains an ethylenically unsaturated group, it can be photo-radical polymerized. The number of ethylenically unsaturated groups per molecule of the (A) component can be 1 or more than 2. In addition, when the (A) component contains more than 2 ethylenically unsaturated groups per molecule, these ethylenically unsaturated groups can be the same or different.
[0016] In addition, since component (A) contains a carboxyl group, the resin composition containing component (A) exhibits solubility in an alkaline solution (for example, a 1 mass % sodium carbonate aqueous solution as an alkaline developer). The number of carboxyl groups per molecule of component (A) may be 1 or 2 or more.
[0017] In the present embodiment, the component (A) includes (A-1) a resin containing a naphthalene skeleton. The component (A) may further include (A-2) an acid-modified epoxy (meth)acrylate resin as required. The component (A-2) is an example of the component (A) other than the component (A-1).
[0018] <(A-1) Naphthalene skeleton-containing resin> Since the component (A-1) is a resin belonging to the component (A), it is a resin containing an ethylenically unsaturated group and a carboxyl group. Therefore, the component (A-1) can be photo-radical polymerized, and the resin composition containing the component (A-1) is soluble in an alkaline solution.
[0019] (A-1) component preferably has a plurality of ethylenically unsaturated groups in 1 molecule.Thus, the mechanical strength and solubility resistance of the cured product of the resin combination can be improved.In addition, (A-1) component preferably has 2 or less ethylenically unsaturated groups for 1 naphthalene skeleton.Thus, the cross-linking position (cross-linking point) can be adjusted, so that the mechanical strength and solubility resistance of the cured product of the resin combination can be controlled.More preferably, the ethylenically unsaturated group is contained in the substituent possessed by the naphthalene skeleton.In order to include the ethylenically unsaturated group in the substituent of the naphthalene skeleton, it can be obtained in the following manner: as the first precursor, for example, a compound in which the H atom of the OH group of naphthol is replaced by a substituent (for example, epoxy, glycidyl) containing an epoxy group is prepared, and a compound (for example, unsaturated carboxylic acid, preferably (methyl) acrylic acid) with an ethylenically unsaturated bond is added to the first precursor.Thus, an ethylenically unsaturated group can be introduced in the substituent possessed by the naphthalene skeleton.
[0020] The component (A-1) preferably has a plurality of carboxyl groups in one molecule. Thus, the solubility of the resin composition in an alkaline solution (e.g., an alkaline developer) can be improved. The component (A-1) preferably has two or less carboxyl groups for one naphthalene skeleton. Thus, the solubility can be controlled. More preferably, the carboxyl group is contained in the substituent possessed by the naphthalene skeleton. In order to make the substituent of the naphthalene skeleton contain a carboxyl group, it can be obtained in the following manner: as a first precursor, for example, a compound in which the H atom of the OH group of naphthol is substituted by a substituent containing an epoxy group is prepared, and a compound having an ethylenically unsaturated bond (e.g., an unsaturated carboxylic acid, preferably (methyl) acrylic acid) is added to the first precursor, thereby obtaining a second precursor having a secondary hydroxyl group, and a carboxylic anhydride (e.g., tetrahydrophthalic acid) is added to the second precursor. Thus, both ethylenically unsaturated groups and carboxyl groups can be introduced into the substituent possessed by the naphthalene skeleton.
[0021] In addition, component (A-1) is a resin containing a naphthalene skeleton. A resin containing a naphthalene skeleton refers to a compound containing one or more naphthalene skeletons in one molecule. Even if the resin composition contains components (C) to (E), component (A-1) can be well blended, so the uneven composition in the resin composition can be suppressed. In addition, component (A-1) can be dissolved at a dissolution rate in an alkaline solution (such as an alkaline developer) at a suitable range. In addition, when the resin composition containing component (A-1) is developed with an alkaline developer, it is possible to suppress the local generation of over-dissolved portions contrary to the intention and insoluble portions contrary to the intention in the resin composition. Therefore, the side erosion resistance of the resin composition can be improved, and preferably, the side of the opening pattern can be made close to vertical relative to the layer plane.
[0022] In addition, when a resin containing a naphthalene skeleton is used as the (A-1) component, the rigidity of the molecule generally increases, so the activity of the molecules in the resin composition can be suppressed, and as a result, the glass transition temperature of the cured product of the resin composition is higher, and the average linear thermal expansion coefficient of the cured product is further reduced. Furthermore, through the action of the (A-1) component, the tolerance of the cured product to the internal stress generated by thermal expansion or thermal contraction is usually improved, so the breakage of the cured product caused by temperature changes can be suppressed.
[0023] The component (A-1) may contain one naphthalene skeleton in one molecule, or may contain two or more naphthalene skeletons.
[0024] The component (A-1) is, for example, a resin containing a structure represented by the following formula (1). The component (A-1) may have a plurality of (e.g., 1 to 10, preferably 1 to 6) structures represented by the following formula (1). When the component (A-1) has a plurality of structures represented by the following formula (1), the component (A-1) may contain these structures represented by the following formula (1) as structural units (repeating units). 1 The bonding bond (chemical bond) can be bonded to any carbon atom that can be bonded among the carbon atoms in the naphthalene skeleton. 1 Bonded bond" and "with R 1 The bond in formula (1) other than OR′ (hereinafter sometimes referred to as “terminal bond”) may be bonded to the carbon atom of the same benzene ring or to the carbon atom of different benzene rings. For example, the terminal bond in the naphthalene skeleton and the bond to R 1 The combination of positions of the bonded coupling bonds may be 1,2, 1,3, 1,4, 1,5, 1,6, 1,7, 1,8, 2,3, 2,6, 2,7 of the naphthalene ring.
[0025] [Chemistry 1]
[0026] In the above formula (1), R 1 and R 2 R each independently represents an alkylene group which may have a substituent. 1 The number of carbon atoms is usually 1 to 20, preferably 1 to 10, and more preferably 1 to 6. The alkylene group may be linear or branched. Examples of the alkylene group include methylene, ethylene, propylene, and butylene.
[0027] R 1 and R 2 Examples of the substituents which may be possessed include, independently, a halogen atom, an alkyl group, an alkoxy group, an aryl group, an arylalkyl group, a silyl group, an acyl group, an acyloxy group, a carboxyl group, a sulfo group, a cyano group, a nitro group, a hydroxyl group, a mercapto group, and an oxo group.
[0028] In the above formula (1), X represents an arylene group which may have a substituent. The carbon number of X is usually 6 to 30, preferably 6 to 20, and more preferably 6 to 10. Examples of the arylene group include phenylene, anthracene, phenanthrenyl, and biphenylene.
[0029] The substituent that X may have includes, for example, 1 and R 2 The substituents which may be possessed are the same as those exemplified above.
[0030] In the above formula (1), a represents 0 or 1. Here, a is the number of groups X.
[0031] In the above formula (1), s represents 0 or 1. Here, s and t are respectively 1 and group R 2 In the above formula (1), t represents 0 or 1. However, regarding s and t, s+t is not 0. However, when a=1, it is preferred that both s and t are 1. When a=0, it is preferred that one of s and t is 0.
[0032] In the above formula (1), OR' is a substituent on the naphthalene skeleton. In the above formula (1), R' each independently represents an organic group containing an ethylenically unsaturated group and a carboxyl group.
[0033] R' preferably represents a group represented by the following formula (2). [Chemistry 2]
[0034] In the above formula (2), R 3 represents a trivalent group, preferably a trivalent hydrocarbon group which may have a substituent (wherein a heteroatom may exist between carbon-carbon bonds (CC bonds)), and preferably a trivalent aliphatic hydrocarbon group which may have a substituent. 3It may be a trivalent residue of an epoxy-containing substituent which may have a substituent. 3 The substituents that may be present include, for example, 1 and R 2 The substituents which may be possessed are the same as those exemplified above.
[0035] In the above formula (2), R 4 represents an organic group containing an ethylenically unsaturated group. A preferred example of an organic group containing an ethylenically unsaturated group is a (meth)acryloyloxy group. The "(meth)acryloyloxy group" includes an acryloyloxy group, a methacryloyloxy group, and a combination thereof.
[0036] In the above formula (2), R 5 An example of an organic group containing a carboxyl group is -OCO-R 6 -COOH. Among them, R 6 represents a divalent group. 6 , preferably a divalent hydrocarbon group which may have a substituent. 6 The number of carbon atoms is usually 1 to 30, preferably 1 to 20, and more preferably 1 to 6. Examples of the divalent hydrocarbon group include linear or branched non-cyclic alkylene groups such as methylene, ethylene, propylene, and butylene; saturated or unsaturated divalent alicyclic hydrocarbon groups; and arylene groups such as phenylene and naphthylene. Among them, divalent alicyclic hydrocarbon groups and arylene groups are preferred, and 4-cyclohexenylene and phenylene groups are particularly preferred. In addition, R 6 The substituents that may be present include, for example, 1 and R 2 The substituents that may be present are the same as those in the examples. 6 -CO-R in -COOH 6 -COOH is usually a residue of a carboxylic anhydride. Examples of carboxylic anhydrides include maleic anhydride, succinic anhydride, itaconic anhydride, phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, trimellitic anhydride, pyromellitic anhydride, and benzophenonetetracarboxylic dianhydride.
[0037] In the above formula (1), c is generally an integer of 1 to 6, preferably 1 to 3, and more preferably 1 to 2. Here, c is the number of groups OR'.
[0038] <(A-1) First example of component (a=1)> A preferred example of the component (A-1) is a naphthol aralkyl type resin. The "naphthol aralkyl type resin" refers to a resin containing a structural group obtained by removing a H atom in an OH group from a naphthol aralkylene group.
[0039] A preferred naphthol aralkyl type resin is a resin having a structure in which a=1 in the above formula (1), for example, a resin having a structure represented by the following formula (3). [Chemistry 3]
[0040] In the above formula (3), R 1 , R 2 , X, s, t, R' and c are the same as above. Preferably, s and t are both 1.
[0041] A more preferred naphthol aralkyl resin is a resin containing a structure in which c=1, s=1 and t=1 in the above formula (3), for example, a naphthol aralkyl resin containing a divalent group having a structure represented by the following formula (4) or (5).
[0042] [Chemistry 4]
[0043] [Chemistry 5]
[0044] In the above formula (4) or (5), R 1 , R 2 , X, R' and c are the same as those described above. The naphthol aralkyl type resin represented by the above formula (4) or (5) is a resin that can be synthesized using the naphthol aralkyl type epoxy resin B used in the following Synthesis Example 2 as a material. The naphthol aralkyl type epoxy resin B can be purchased, for example, as "ESN-475V" (epoxy equivalent 325) manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd.
[0045] <(A-1) Second example of component (a=0)> Among the components (A-1), preferred examples other than naphthol aralkyl type resins (a=0) are resins containing a structure in which c=2, s=1 and t=0 in the above formula (1), for example, resins containing a naphthalene skeleton containing a divalent group having a structure represented by the following formula (6). [Chemistry 6]
[0046] In the above formula (6), R 1 , R and R' are the same as above. The resin containing a naphthalene skeleton represented by the above formula (6) is a resin that can be synthesized using an epoxy resin A containing a naphthalene skeleton (1,1'-bis(2,7-diepoxypropoxynaphthyl)methane, epoxy equivalent 162) as a material (refer to the following synthesis example 1). The epoxy resin A containing a naphthalene skeleton can be purchased, for example, as "EXA-4700" manufactured by Dainippon Ink and Chemicals Co., Ltd.
[0047] The weight average molecular weight of the component (A-1) is preferably 500 or more, more preferably 1000 or more, further preferably 1500 or more, and further more preferably 2000 or more from the viewpoint of film-forming properties. The upper limit is preferably 10000 or less, more preferably 8000 or less, and further preferably 7500 or less from the viewpoint of developability. The weight average molecular weight is a weight average molecular weight measured by gel permeation chromatography (GPC) in terms of polystyrene conversion.
[0048] As the acid value of component (A-1), from the viewpoint of improving the solubility of the resin composition in an alkaline solution, it is preferably 0.1 mgKOH / g, 0.5 mgKOH / g or more or 1 mgKOH / g or more. On the other hand, from the viewpoint of suppressing the dissolution of the fine pattern of the cured product in an alkaline solution and improving the side corrosion resistance, the acid value is preferably 150 mgKOH / g or less, more preferably 120 mgKOH / g or less, and further preferably 100 mgKOH / g or less. Here, the acid value refers to the residual acid value of the carboxyl group present in component (A-1), and the acid value can be measured by the following method. First, after accurately weighing about 1 g of the measured resin solution, 30 g of acetone is added to the resin solution to uniformly dissolve the resin solution. Next, an appropriate amount of phenolphthalein as an indicator is added to the solution, and titration is performed using a 0.1 N KOH aqueous solution. Then, the acid value is calculated using the following formula (7). Formula: A = 10 × Vf × 56.1 / (Wp × I) (7)
[0049] In the above formula (7), A represents the acid value [mgKOH / g], Vf represents the titration amount of KOH [mL], Wp represents the mass of the measured resin solution [g], and I represents the ratio of the nonvolatile component of the measured resin solution [mass %].
[0050] (A-1) Weighted average S of the dissolution rate [nm / sec] of the component in the alkaline solution based on the mass ratio (A-1) Preferably, the following formula (II) is satisfied: 5≤S (A-1) ≤110···(II). The dissolution rate in an alkaline solution can be measured, for example, by the method described in the Examples. More specifically, the weighted average S of the dissolution rate of the component (A-1) is (A-1) It is more preferably 6 nm / sec or more, further preferably 10 nm / sec or more, particularly preferably 15 nm / sec or more, preferably 100 nm / sec or less, more preferably 90 nm / sec or less, and further preferably 80 nm / sec or less. (A-1)Within the above range, the dissolution rate of the resin composition in the alkaline developer can be suppressed from becoming too slow or too fast. Therefore, it is possible to suppress the generation of excessively dissolved parts contrary to the intention and undissolved parts contrary to the intention locally. Therefore, the side erosion resistance can be improved, and preferably, the side of the opening pattern can be made close to vertical relative to the layer plane.
[0051] It is further preferred that when a plurality of naphthalene skeleton-containing resins are used as the component (A-1), the dissolution rate [nm / sec] of each of the naphthalene skeleton-containing resins is within the above range. (A-1) The above range can be reliably satisfied.
[0052] Regarding component (A-1), from the viewpoint of adjusting the solubility of the resin composition in an alkaline solution, when the non-volatile component in component (A) is set to 100% by mass, it is preferred that the content of component (A-1) is 5% by mass or more, more preferably 10% by mass or more, and further preferably 20% by mass or more. The upper limit is usually 100% by mass or less, and from the viewpoint of improving the side corrosion resistance, it is preferably 80% by mass or less, more preferably 70% by mass or less, and further preferably 60% by mass or less.
[0053] Regarding (A-1) component, from the viewpoint of regulating the solubility of the resin combination in the alkaline solution, when the non-volatile component in the resin combination is set to 100% by mass, it is preferred that the content of (A-1) component is 5% by mass or more, more preferably 10% by mass or more, and further preferably 15% by mass or more. From the viewpoint of improving the side corrosion resistance, the upper limit is preferably 30% by mass or less, more preferably 29% by mass or less, and further preferably 28% by mass or less.
[0054] <Method for producing component (A-1)> (A-1) component is not limited to the above-mentioned example as long as it is a compound with a resin containing a naphthalene skeleton, an ethylenically unsaturated group and a carboxyl group. It is not particularly limited. As one of its modes, it is possible to cite a naphthalene-type epoxy compound (epoxy compound containing a naphthalene skeleton) having a naphthalene skeleton and an unsaturated carboxylic acid reaction, and further react with a carboxylic anhydride to obtain an acid-modified unsaturated epoxy ester resin containing a naphthalene skeleton. The manufacture method for the acid-modified unsaturated epoxy ester resin containing a naphthalene skeleton is described. First, the epoxy compound containing a naphthalene skeleton is reacted with an unsaturated carboxylic acid to obtain an unsaturated epoxy ester resin containing a naphthalene skeleton, and then the unsaturated epoxy ester resin containing a naphthalene skeleton is reacted with a carboxylic anhydride. In this way, an acid-modified unsaturated epoxy ester resin containing a naphthalene skeleton can be obtained.
[0055] As the epoxy compound containing a naphthalene skeleton, any compound having one or more epoxy groups in the molecule can be used, and examples thereof include monohydroxynaphthalene epoxy resins, dihydroxynaphthalene epoxy resins, polyhydroxybinaphthyl epoxy resins, naphthalene epoxy resins obtained by condensation reaction of polyhydroxynaphthalene with aldehydes, binaphthol epoxy resins, naphthalene epoxy resins having a naphthalene skeleton in the molecule, etc. These compounds may be used alone or in combination of two or more.
[0056] Examples of the monohydroxynaphthalene epoxy resin include 1-glycidyloxynaphthalene and 2-glycidyloxynaphthalene, and examples of the dihydroxynaphthalene epoxy resin include 1,3-diglycidyloxynaphthalene, 1,4-diglycidyloxynaphthalene, 1,5-diglycidyloxynaphthalene, 1,6-diglycidyloxynaphthalene, 2,3-diglycidyloxynaphthalene, 2,6-diglycidyloxynaphthalene, and 2,7-diglycidyloxynaphthalene.
[0057] Examples of the polyhydroxybinaphthyl epoxy resin include 1,1′-bi(2-glycidyloxy)naphthalene, 1-(2,7-diglycidyloxy)-1′-(2′-glycidyloxy)binaphthyl, and 1,1′-bi(2,7-diglycidyloxy)naphthalene.
[0058] Examples of naphthalene-type epoxy resins obtained by condensation reaction of polyhydroxynaphthalene and aldehydes include 1,1'-bis(2,7-diglycidylnaphthyl)methane, 1-(2,7-diglycidylnaphthyl)-1'-(2'-glycidylnaphthyl)methane, and 1,1'-bis(2-glycidylnaphthyl)methane.
[0059] Among them, polyhydroxybinaphthyl epoxy resins having two or more naphthalene skeletons in one molecule and naphthalene-type epoxy resins obtained by a condensation reaction of polyhydroxynaphthalene and aldehydes are preferred. In particular, 1,1'-bis(2,7-diglycidyloxynaphthyl)methane, 1-(2,7-diglycidyloxynaphthyl)-1'-(2'-glycidyloxynaphthyl)methane, 1-(2,7-diglycidyloxy)-1'-(2'-glycidyloxy)binaphthyl, and 1,1'-bi(2,7-diglycidyloxy)naphthalene, each having three or more epoxy groups in one molecule, are preferred from the viewpoint of excellent average linear thermal expansion coefficient and excellent heat resistance.
[0060] As unsaturated carboxylic acids, for example, acrylic acid, methacrylic acid, cinnamic acid, crotonic acid, etc. can be cited. These unsaturated carboxylic acids can be used alone or in combination of two or more. Among them, from the viewpoint of improving the photocurability of the photosensitive resin composition, acrylic acid and methacrylic acid are preferred. It should be noted that in this specification, the reaction product of the above-mentioned naphthalene-type epoxy compound and (meth)acrylic acid, i.e., the naphthalene-type epoxy compound ester resin, is sometimes recorded as "naphthalene-type epoxy compound (meth)acrylate", where the epoxy group of the naphthalene-type epoxy compound generally substantially disappears due to the reaction with (meth)acrylic acid. "(Meth)acrylate" includes methacrylate, acrylate and a combination thereof. Acrylic acid and methacrylic acid are sometimes collectively referred to as "(meth)acrylic acid".
[0061] Examples of the carboxylic anhydride include maleic anhydride, succinic anhydride, itaconic anhydride, phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, trimellitic anhydride, pyromellitic anhydride, and benzophenonetetracarboxylic anhydride. Any of these carboxylic anhydrides may be used alone, or two or more thereof may be used in combination. Among these, succinic anhydride and tetrahydrophthalic anhydride are preferred from the viewpoint of improving the developability and insulation reliability of the cured product.
[0062] When obtaining the acid-modified unsaturated naphthalene skeleton-containing epoxy ester resin, an unsaturated carboxylic acid and a naphthalene skeleton-containing epoxy compound may be reacted in the presence of a catalyst to obtain the unsaturated naphthalene skeleton-containing epoxy ester resin, and then the unsaturated naphthalene skeleton-containing epoxy ester resin may be reacted with a carboxylic anhydride.
[0063] The amount of the catalyst used in this case is preferably 2% by mass or less, more preferably 0.0005% to 1% by mass, and even more preferably 0.001% to 0.5% by mass, based on the total mass of the unsaturated carboxylic acid, the naphthalene skeleton-containing epoxy compound and the carboxylic anhydride. Examples of the catalyst include N-methylmorpholine, pyridine, 1,8-diazabicyclo[5.4.0]undecene-7 (DBU), 1,5-diazabicyclo[4.3.0]nonene-5 (DBN), 1,4-diazabicyclo[2.2.2]octane (DABCO), tri-n-butylamine or dimethylbenzylamine, butylamine, octylamine, monoethanolamine, diethanolamine, triethanolamine, imidazole, 1-methylimidazole, 2,4-dimethylimidazole, 1,4-diethylimidazole, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-(N-phenyl)aminopropyltrimethoxysilane, 3-(2-aminoethyl)aminopropyltrimethoxysilane, 3-(2-aminoethyl)aminopropyltrimethoxysilane, Various amine compounds such as trimethylphosphine, tributylphosphine, triphenylphosphine, etc.; phosphines such as tetramethylphosphonium salt, tetraethylphosphonium salt, tetrapropylphosphonium salt, tetrabutylphosphonium salt, trimethyl (2-hydroxypropyl) phosphonium salt, triphenylphosphonium salt, benzylphosphonium salt, etc., among which there are phosphonium salts having chloride ion, bromide ion, carboxylate ion, hydroxide ion, etc. as representative counter anions; sulfonium salts such as trimethylsulfonium salt, benzyltetramethylenesulfonium salt, phenylbenzylmethylsulfonium salt or phenyldimethylsulfonium salt, among which there are sulfonium salts having carboxylate ion, hydroxide ion, etc. as representative counter anions; acidic compounds such as phosphoric acid, p-toluenesulfonic acid, sulfuric acid, etc. The reaction can be carried out in the range of 50°C to 150°C, preferably in the range of 80°C to 120°C.
[0064] When obtaining the acid-modified unsaturated naphthalene skeleton-containing epoxy ester resin, an organic solvent may be used. As the organic solvent, the same organic solvent as the organic solvent (F) described below may be used.
[0065] When obtaining an acid-modified unsaturated naphthalene skeleton-containing epoxy ester resin, a polymerization inhibitor such as hydroquinone may also be used. The amount of the polymerization inhibitor used in this case is preferably 2% by mass or less, more preferably in the range of 0.0005% by mass to 1% by mass, and further preferably in the range of 0.001% by mass to 0.5% by mass, relative to the total mass of the unsaturated carboxylic acid, the naphthalene skeleton-containing epoxy compound and the carboxylic anhydride.
[0066] As the acid-modified unsaturated epoxy ester resin containing a naphthalene skeleton, an acid-modified epoxy (meth) acrylate containing a naphthalene skeleton is preferred. The acid-modified epoxy (meth) acrylate containing a naphthalene skeleton refers to an acid-modified unsaturated epoxy ester resin containing a naphthalene skeleton obtained by using an epoxy compound containing a naphthalene skeleton and (meth) acrylic acid as an unsaturated carboxylic acid.
[0067] As other forms of the component (A-1), there can be mentioned: a (meth) acrylic resin having a structural unit obtained by polymerizing (meth) acrylic acid, and an unsaturated modified (meth) acrylic resin containing a naphthalene skeleton into which an ethylenically unsaturated group is introduced by reacting an epoxy compound containing an ethylenically unsaturated group and a naphthalene skeleton. Furthermore, a carboxylic anhydride can be reacted with a hydroxyl group generated when an unsaturated group is introduced. As the carboxylic anhydride, the same substances as those of the above-mentioned acid anhydride can be used, and the preferred range is also the same.
[0068] <(A-2) Acid-modified epoxy (meth)acrylate resin> The acid-modified epoxy (meth)acrylate resin as the component (A-2) is a compound having a structure in which a carboxyl group is introduced into a (meth)acrylate of an epoxy compound. However, the component (A-2) does not contain the component (A-1).
[0069] As one embodiment of the component (A-2), an acid-modified bisphenol epoxy (meth)acrylate obtained by reacting a bisphenol epoxy compound such as a bisphenol A epoxy compound or a bisphenol F epoxy compound with (meth) acrylic acid and further reacting with a carboxylic anhydride can be mentioned. Specifically, a bisphenol epoxy (meth)acrylate can be obtained by reacting a bisphenol epoxy compound with (meth) acrylic acid, and then reacting the bisphenol epoxy (meth)acrylate with a carboxylic anhydride to obtain an acid-modified bisphenol epoxy (meth)acrylate.
[0070] As another embodiment of the component (A-2), an acid-modified biphenyl epoxy (meth)acrylate obtained by reacting a biphenyl epoxy compound with (meth) acrylic acid and further reacting with carboxylic anhydride can be mentioned. Specifically, a biphenyl epoxy (meth)acrylate can be obtained by reacting a biphenyl epoxy compound with (meth) acrylic acid, and then reacting the biphenyl epoxy (meth)acrylate with carboxylic anhydride to obtain an acid-modified biphenyl epoxy (meth)acrylate.
[0071] As a further embodiment of the component (A-2), an acid-modified epoxy (meth)acrylate obtained by reacting an epoxy compound other than the above-mentioned epoxy compound with (meth)acrylic acid and further reacting with a carboxylic anhydride can be cited. Such epoxy compounds include, for example, novolac-type epoxy resins such as phenol novolac-type epoxy resins, cresol novolac-type epoxy resins, bisphenol A novolac-type epoxy resins, and alkylphenol novolac-type epoxy resins; fluorine-containing epoxy resins such as perfluoroalkyl epoxy resins, bixylenol-type epoxy resins; dicyclopentadiene-type epoxy resins; trisphenol-type epoxy resins; tert-butyl-catechol-type epoxy resins; epoxy resins containing condensed ring skeletons such as anthracene-type epoxy resins; glycidylamine-type epoxy resins; and epoxy resins containing condensed ring skeletons such as cyclopentadiene-type epoxy resins. Water glyceryl ester type epoxy resin; linear aliphatic epoxy resin; epoxy resin with butadiene structure; alicyclic epoxy resin; heterocyclic epoxy resin; epoxy resin containing spiro ring; cyclohexanedimethanol type epoxy resin; trimethylol type epoxy resin; tetraphenylethane type epoxy resin; acrylic resin containing glycidyl group such as poly(meth)acrylate glycidyl ester, copolymer of glycidyl methacrylate and acrylate; fluorene type epoxy resin; halogenated epoxy resin, etc.
[0072] Such acid-modified epoxy (meth)acrylates can be commercially available products, and specific examples thereof include: "ZAR-2000" manufactured by Nippon Kayaku Co., Ltd. (acid-modified bisphenol epoxy acrylate: a reaction product of bisphenol A epoxy resin, acrylic acid, and succinic anhydride), "ZFR-1491H" (acid-modified bisphenol epoxy acrylate: a reaction product of bisphenol F epoxy resin, acrylic acid, and acid anhydride), "ZFR-1533H" (acid-modified bisphenol epoxy acrylate: a reaction product of bisphenol F epoxy resin, acrylic acid, and tetrahydrophthalic anhydride), "ZCR-1569H" (acid-modified biphenyl epoxy acrylate: a reaction product of biphenyl epoxy resin, acrylic acid, and acid anhydride), and "PR-300CP" manufactured by Showa Denko K.K. (a reaction product of cresol novolac epoxy resin, acrylic acid, and acid anhydride). These substances may be used alone or in combination of two or more.
[0073] As other forms of component (A-2), there can be listed: (meth) acrylic resin having a structural unit obtained by polymerizing (meth) acrylic acid, and unsaturated modified (meth) acrylic resin introduced with an ethylenically unsaturated group by reacting with a (meth) acrylic ester of an epoxy compound. Examples of (meth) acrylic esters of epoxy compounds include glycidyl methacrylate, 4-hydroxybutyl (meth) acrylic acid glycidyl ether, and 3,4-epoxycyclohexylmethyl (meth) acrylic acid. Furthermore, the hydroxyl group generated when the unsaturated group is introduced can also be reacted with a carboxylic anhydride. As the carboxylic anhydride, the same substance as the above-mentioned carboxylic anhydride can be used, and the preferred range is also the same.
[0074] As such unsaturated modified (meth)acrylic resin, commercially available products can be used. Specific examples thereof include "SPC-1000" and "SPC-3000" manufactured by Showa Denko K.K., and "CYCLOMER P(ACA)Z-250", "CYCLOMER P(ACA)Z-251", "CYCLOMER P(ACA)Z-254", "CYCLOMER P(ACA)Z-300", and "CYCLOMER P(ACA)Z-320" manufactured by Daicel-Allenex K.K.
[0075] The weight average molecular weight of the component (A-2) is preferably 1000 or more, more preferably 1500 or more, and further preferably 2000 or more from the viewpoint of film-forming properties. The upper limit is preferably 20000 or less, more preferably 15000 or less, and further preferably 14000 or less from the viewpoint of developability. The weight average molecular weight is a weight average molecular weight measured by gel permeation chromatography (GPC) in terms of polystyrene conversion.
[0076] As the acid value of (A-2) component, from the viewpoint of improving the solubility of the resin composition in an alkaline solution, the acid value is preferably more than 0.1 mgKOH / g, more preferably more than 0.5 mgKOH / g, and further preferably more than 1 mgKOH / g. On the other hand, from the viewpoint of suppressing the dissolution of the fine pattern of the cured product in an alkaline solution and improving the side erosion resistance, the acid value is preferably less than 150 mgKOH / g, more preferably less than 120 mgKOH / g, and further preferably less than 100 mgKOH / g. Here, the acid value refers to the residual acid value of the carboxyl group present in the (A-2) component, and the acid value can be measured using the aforementioned method.
[0077] (A-2) Weighted average S of the dissolution rate [nm / sec] of the component in the alkaline solution based on the mass ratio (A-2) Preferably, the following formula (III) is satisfied: 1≤S (A-2)≤150···(III) More preferably, the following formula (IIIa) is satisfied: 1≤S (A-2) ≤131···(IIIa). Thus, by adjusting the solubility of the resin composition in an alkaline solution in consideration of the content of the component (A-1), the side corrosion resistance can be controlled. The dissolution rate can be measured by the method described in the Examples, for example.
[0078] It is further preferred that when a plurality of acid-modified epoxy (meth)acrylate resins are used as component (A-2), the dissolution rate [nm / sec] of each of the acid-modified epoxy (meth)acrylate resins is more preferably within the above range. (A-2) The above range can be reliably satisfied.
[0079] About (A-2) component, from the viewpoint of adjusting solubility in alkaline solution, when the non-volatile component of (A) component is set to 100% by mass, it is preferred that the content of (A-2) component is the same as the content of (A-1) component or less than the content of (A-1) component, more preferably when the non-volatile component of (A) component is set to 100% by mass, the content of (A-2) component is 50% by mass or less of the content of (A-1) component, and more preferably 45% by mass or less. When the non-volatile component of resin composition is set to 100% by mass, from the viewpoint of adjusting the solubility of resin composition in alkaline solution, the content of (A-2) component is preferably 30% by mass or less, more preferably 20% by mass or less, and more preferably 15% by mass or less, and the lower limit is usually 0% by mass, but when used in combination with (A-1) component, the lower limit can be set to 0.1% by mass or 0.2% by mass.
[0080] The component (A-2) is preferably used in combination with the component (A-1) from the viewpoint of heat resistance and mechanical strength, for example, adjustment of the average linear thermal expansion coefficient and the glass transition temperature.
[0081] <(A-3) Any resin containing an ethylenically unsaturated group and a carboxyl group> The component (A) may further contain (A-3) an arbitrary resin containing an ethylenically unsaturated group and a carboxyl group in combination with the components (A-1) and (A-2). The component (A-3) does not contain the components (A-1) and (A-2).
[0082] The weight average molecular weight and acid value of the component (A-3) are arbitrary, but are preferably in the same range as those of the component (A-2). Thus, the same advantages as those described in the item of the component (A-2) can be obtained.
[0083] <(A) Overall properties of components> The weight average molecular weight of component (A) is preferably 500 or more or 1000 or more, more preferably 1500 or more, and further preferably 2000 or more from the viewpoint of film-forming properties as the lower limit. It is preferably 20000 or less, more preferably 15000 or less, and further preferably 14500 or less from the viewpoint of developability as the upper limit. The weight average molecular weight is a weight average molecular weight in terms of polystyrene measured by gel permeation chromatography (GPC).
[0084] (A) Weighted average S of the dissolution rate [nm / sec] of the component in the alkaline solution based on the mass ratio (A) Preferably, the following formula (I) is satisfied: 5≤S (A) ≤110···(I). The dissolution rate in an alkaline solution can be measured, for example, by the method described in the Examples. More specifically, the weighted average S of the dissolution rate of the component (A) (A) It is usually 5 nm / sec or more, more preferably 10 nm / sec or more, and even more preferably 15 nm / sec or more, and usually 110 nm / sec or less, preferably 100 nm / sec or less, more preferably 90 nm / sec or less, and even more preferably 80 nm / sec or less. (A) Being in the above range, the dissolution rate of the resin composition in the alkaline developer can be suppressed from becoming too slow or too fast. Therefore, it is possible to suppress the generation of excessively dissolved parts contrary to the intention and undissolved parts contrary to the intention locally. Therefore, the side erosion resistance can be improved, and preferably the side of the opening pattern can be made close to vertical relative to the layer plane.
[0085] It is further preferred that when a plurality of resins containing ethylenically unsaturated groups and carboxyl groups are used as component (A), the dissolution rates [nm / sec] of the resins containing ethylenically unsaturated groups and carboxyl groups are each preferably within the above range. (A) The above range can be reliably satisfied.
[0086] Regarding component (A), from the viewpoint of adjusting the solubility of the resin composition in an alkaline solution, when the non-volatile component in the resin composition is set to 100% by mass, it is preferred that the content of component (A) is 10% by mass or more, more preferably 15% by mass or more, and further preferably 20% by mass or more. From the viewpoint of improving side corrosion resistance, the upper limit is preferably 30% by mass or less, more preferably 29.5% by mass or less, and further preferably 29% by mass or less.
[0087] <(B) Inorganic filler having an average particle size of 0.5 μm or more> The resin composition contains (B) an inorganic filler having an average particle size of 0.5 μm or more. Even if the resin composition contains the (B) component (that is, even when the average particle size of the inorganic filler is large), a resin composition can be provided that can obtain a cured product with excellent side erosion resistance. In addition, by using the (B) component, the average linear thermal expansion coefficient of the cured product can usually be reduced.
[0088] The material of inorganic filler is not particularly limited, and for example can be enumerated: silicon dioxide, aluminum oxide, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate, barium zirconate, calcium zirconate, zirconium phosphate and zirconium tungstate phosphate etc.Wherein, silicon dioxide is particularly suitable.In addition, as silicon dioxide, preferably spherical silicon dioxide.About inorganic filler, can use 1 kind alone, also can use 2 or more kinds in combination.
[0089] From the viewpoint of obtaining a cured product with excellent side erosion resistance, the average particle size of the inorganic filler is 0.5 μm or more, preferably 0.8 μm or more, and more preferably 1 μm or more. From the viewpoint of suppressing light reflection during exposure and obtaining excellent developability, the upper limit of the average particle size is preferably 2.5 μm or less, more preferably 2 μm or less, further preferably 1.5 μm or less, and further more preferably 1.3 μm or less. As a commercially available product of an inorganic filler with such an average particle size, for example, can be cited: "SC4050", "ADMAFINE" made by Yaduma (Admatechs), "SFP Series" made by Electric Chemical Industry, "SP (H) Series" made by Nippon Steel and Sumitomo Metal Materials, "Sciqas Series" made by Sakai Chemical Industry, "Seahostar Series" made by Nippon Shokubai, "AZ Series" made by Nippon Steel and Sumitomo Metal Materials, "AX Series" made by Sakai Chemical Industry, "B Series" made by Sakai Chemical Industry, "BF Series" made by Sakai Chemical Industry, etc.
[0090] The average particle size of the inorganic filler can be measured by laser diffraction-scattering method based on Mie scattering theory. Specifically, it can be measured in the following manner: using a laser diffraction scattering particle size distribution measuring device, the particle size distribution of the inorganic filler is made on a volume basis, and the median particle size is used as the average particle size. Regarding the measurement sample, it is preferred to use a sample obtained by dispersing the inorganic filler in water using ultrasound. As a laser diffraction scattering particle size distribution measuring device, "LA-500" made by Horiba, Ltd., "SALD-2200" made by Shimadzu, Ltd., etc. can be used.
[0091] From the viewpoint of obtaining a cured product having excellent side corrosion resistance, the specific surface area of the inorganic filler is preferably 1 m 2 / g or more, more preferably 3m 2 / g or more, particularly preferably 5 m 2 There is no particular upper limit, but it is preferably 60 m 2 / g or less, 50m 2 / g or below or 40m 2 The specific surface area can be obtained by adsorbing nitrogen gas on the surface of a sample using a specific surface area measuring device (Macsorb HM-1210 manufactured by MOUNTECH) according to the BET method and calculating the specific surface area using the BET multipoint method.
[0092] From the viewpoint of improving moisture resistance and dispersibility, the inorganic filler is preferably surface-treated with one or more surface treatment agents such as aminosilane coupling agents, epoxysilane coupling agents, mercaptosilane coupling agents, silane coupling agents, alkoxysilane compounds, organosilazane compounds, and titanate coupling agents. Commercially available products of the surface treatment agent include, for example, "KBM403" (3-glycidoxypropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., "KBM803" (3-mercaptopropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., "KBE903" (3-aminopropyltriethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., "KBM573" (N-phenyl-3-aminopropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., "SZ-31" (hexamethyldisilazane) manufactured by Shin-Etsu Chemical Co., Ltd., "KBM103" (phenyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., and "KBM-4803" (long-chain epoxy-type silane coupling agent) manufactured by Shin-Etsu Chemical Co., Ltd.
[0093] Regarding the content of component (B), from the viewpoint of obtaining a cured product with a low average linear thermal expansion coefficient, when the non-volatile component in the resin composition is set to 100% by mass, the content is preferably 60% by mass or more, more preferably 60.5% by mass or more, and further preferably 61% by mass or more. From the viewpoint of obtaining excellent developability by suppressing light reflection during exposure, the upper limit is, for example, 90% by mass or less, 85% by mass or less, 82% by mass or less, or 80% by mass or less.
[0094] <(C) Epoxy resin> The resin composition contains (C) epoxy resin. By containing (C) component, the reaction between (C) components or the reaction between (C) component and (A) component becomes possible, and the mechanical strength and solubility resistance of the cured product of the resin composition can be improved. However, the so-called (C) component here does not include the epoxy resin belonging to (A) component.
[0095] As the component (C), for example, fluorine-containing epoxy resins such as bisphenol AF epoxy resins and perfluoroalkyl epoxy resins can be cited; bisphenol A epoxy resins; bisphenol F epoxy resins; bisphenol S epoxy resins; dimethylol epoxy resins; dicyclopentadiene epoxy resins; trisphenol epoxy resins; naphthol novolac epoxy resins; phenol novolac epoxy resins; tert-butyl-catechol epoxy resins; naphthalene epoxy resins; naphthol epoxy resins; anthracene epoxy resins; glycidylamine epoxy resins; glycidylester epoxy resins Resin; cresol novolac type epoxy resin; biphenyl type epoxy resin; linear aliphatic epoxy resin; epoxy resin with butadiene structure; alicyclic epoxy resin, alicyclic epoxy resin with ester skeleton; heterocyclic epoxy resin; epoxy resin containing spiro ring; cyclohexanedimethanol type epoxy resin; naphthylene ether type epoxy resin; trimethylol type epoxy resin; tetraphenylethane type epoxy resin, halogenated epoxy resin, etc., from the viewpoint of improving adhesion, preferably bisphenol F type epoxy resin, biphenyl type epoxy resin, more preferably biphenyl type epoxy resin. In addition, from the viewpoint of improving heat resistance, preferably naphthalene type epoxy resin, naphthol type epoxy resin, anthracene type epoxy resin, naphthylene ether type epoxy resin, tetraphenylethane type epoxy resin, more preferably tetraphenylethane type epoxy resin. One epoxy resin can be used alone, or two or more epoxy resins can be used in combination. From the viewpoint of improving adhesion and heat resistance, the component (C) preferably contains at least one of a biphenyl type epoxy resin and a tetraphenylethane type epoxy resin, and more preferably contains both of them.
[0096] The epoxy resin preferably contains an epoxy resin having two or more epoxy groups in one molecule. When the non-volatile component of the epoxy resin is set to 100% by mass, it is preferred that at least 50% by mass or more is an epoxy resin having two or more epoxy groups in one molecule. As component (C), two or more epoxy resins may also be used in combination.
[0097] Specific examples of epoxy resins include: "HP4032", "HP4032D", "HP4032SS", and "HP4032H" (naphthalene-type epoxy resins) manufactured by DIC Corporation, "828US", "jER828EL" (bisphenol A-type epoxy resins), "jER807" (bisphenol F-type epoxy resins), "jER152" (phenol novolac-type epoxy resins), "630", and "630LSD" (glycidylamine-type epoxy resins) manufactured by Nippon Steel & Sumitomo Metal Chemicals, Inc., "ZX1059" (a mixture of bisphenol A-type epoxy resin and bisphenol F-type epoxy resin), "YD-8125G" (bisphenol A-type epoxy resin) manufactured by Nippon Steel & Sumitomo Metal Chemicals, Inc., "EX-721" (glycidyl ester-type epoxy resin) manufactured by Nagase ChemteX, and "CELLOXIDE 2021P" (alicyclic epoxy resin with ester skeleton), "PB-3600" (epoxy resin with butadiene structure), "ZX1658" and "ZX1658GS" (liquid 1,4-glycidylcyclohexane), "630LSD" manufactured by Mitsubishi Chemical Corporation (glycidylamine type epoxy resin), "E-7432" and "E-7632" manufactured by Daikin Industries (perfluoroalkyl type epoxy resin), DI "HP-4700", "HP-4710" (naphthalene-type tetrafunctional epoxy resin), "N-690" (cresol novolac-type epoxy resin), "N-695" (cresol novolac-type epoxy resin), "HP-7200", "HP-7200HH", "HP-7200H" (dicyclopentadiene-type epoxy resin), "EXA-7311", "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", "HP6000" (naphthylene ether-type epoxy resin), "EPPN-502H" (trisphenol-type epoxy resin), "NC7000L" (naphthol novolac-type epoxy resin), "NC3000H", "NC3000", "NC3000L", "NC3100" (epoxy resin) manufactured by Nippon Kayaku Co., Ltd. ” (biphenyl type epoxy resin), “ESN475V” (naphthol aralkyl type epoxy resin) manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd., “ESN485” (naphthol novolac type epoxy resin), “YSLV-80XY” (tetramethylbisphenol F type epoxy resin), “YX4000H”, “YL6121” (biphenyl type epoxy resin), “YX4000HK” (biphenyl type epoxy resin), “YX8800” (anthracene type epoxy resin) manufactured by Mitsubishi Chemical Corporation, “PG-100”, “CG-500” manufactured by Osaka Gas Chemical Co., Ltd., “YL7800” (fluorene type epoxy resin) manufactured by Mitsubishi Chemical Corporation, “1010” (solid bisphenol A type epoxy resin), “1031S” (tetraphenylethane type epoxy resin), “YL7760” (bisphenol AF type epoxy resin) manufactured by Mitsubishi Chemical Corporation, etc.,
[0098] About the content of (C) component, from the viewpoint of improving the mechanical strength and solubility resistance of the cured product of the resin composition, when the non-volatile component of the resin composition is set to 100% by mass, the content is preferably 1% by mass or more, more preferably 5% by mass or more, and further preferably 8% by mass or more. The upper limit of the content of epoxy resin is not particularly limited as long as the effect of the present invention can be achieved, and is preferably 25% by mass or less, more preferably 20% by mass or less, and further preferably 15% by mass or less.
[0099] The epoxy equivalent of the epoxy resin is preferably 50 g / eq. to 5000 g / eq., more preferably 50 g / eq. to 3000 g / eq., further preferably 80 g / eq. to 2000 g / eq., and further more preferably 110 g / eq. to 1000 g / eq.. By being within this range, the crosslinking density of the cured product of the resin composition becomes sufficient, and an insulating layer with a small surface roughness can be obtained. It should be noted that the epoxy equivalent can be measured according to JIS K7236, and is the mass of a resin containing 1 equivalent of epoxy groups.
[0100] The weight average molecular weight of the epoxy resin is preferably 100 to 5000, more preferably 250 to 3000, and even more preferably 400 to 1500. Here, the weight average molecular weight of the epoxy resin is a weight average molecular weight in terms of polystyrene measured by gel permeation chromatography (GPC).
[0101] <(D) Photopolymerization initiator> The resin composition contains (D) a photopolymerization initiator. By containing the component (D), the resin composition can be photocured efficiently.
[0102] (D) component is not particularly limited, and examples thereof include: α-aminophenyl alkyl ketone photopolymerization initiators such as 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-[4-(4-morpholinyl)phenyl]-1-butanone, and 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinyl-1-propanone; oxime ester photopolymerization initiators such as 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-ethanone 1-(O-acetoxime); benzophenone, methyl benzophenone, o-phenyl benzoate; Formylbenzoic acid, benzoylethyl ether, 2,2-diethoxyacetophenone, 2,4-diethylthioxanthone, diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide, ethyl-(2,4,6-trimethylbenzoyl)phenylphosphinate, 4,4'-bis(diethylamino)benzophenone, 1-hydroxy-cyclohexyl-phenyl ketone, 2,2-dimethoxy-1,2-diphenylethane-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propane-1-one, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, and the like, in addition to sulfonium salt-based photopolymerization initiators, etc. These photopolymerization initiators may be used alone or in combination of two or more.
[0103] Specific examples of the component (D) include "Omnirad 907", "Omnirad 369", "Omnirad 379", "Omnirad 819", and "Omnirad TPO" manufactured by IGM, "Irgacure TPO", "Irgacure OXE-01", and "Irgacure OXE-02" manufactured by BASF, and "N-1919" manufactured by ADEKA.
[0104] About the content of (D) component, from the viewpoint of making the resin composition fully photocurable, improving the mechanical strength and solubility resistance of the cured product of the resin composition, when the non-volatile component of the resin composition is set to 100% by mass, it is preferably 0.01% by mass or more, more preferably 0.03% by mass or more, and further preferably 0.05% by mass or more. On the other hand, from the viewpoint of suppressing the decline in developability caused by being too sensitive, for the upper limit, it is preferably 2% by mass or less, more preferably 1% by mass or less, and further preferably 0.5% by mass or less.
[0105] Furthermore, the resin composition may contain tertiary amines such as ethyl N,N-dimethylaminobenzoate, isopentyl N,N-dimethylaminobenzoate, amyl 4-dimethylaminobenzoate, triethylamine, triethanolamine, etc. as photopolymerization initiation aids in combination with component (D), or may contain photosensitizers such as pyrazolines, anthracenes, coumarins, xanthones, thioxanthones, etc. These compounds may be used alone or in combination of two or more.
[0106] <(E) Reactive diluent> The resin composition may further contain (E) an active diluent. By containing the (E) component, the optical activity (optical reactivity) can be improved. As the (E) component, for example, a photosensitive (meth)acrylate compound having one or more (meth)acryloyl groups in one molecule and being liquid, solid or semisolid at 25° C. can be used. "(Meth)acryloyl" refers to acryloyl and methacryloyl.
[0107] Representative photosensitive (meth)acrylate compounds include, for example, hydroxyalkyl acrylates such as 2-hydroxyethyl acrylate and 2-hydroxybutyl acrylate; monoacrylates or diacrylates of glycols such as ethylene glycol, methoxytetraglycol, polyethylene glycol, and propylene glycol; acrylamides such as N,N-dimethylacrylamide and N-hydroxymethylacrylamide; aminoalkyl acrylates such as N,N-dimethylaminoethyl acrylate; polyacrylates of polyols such as trimethylolpropane, pentaerythritol, and dipentaerythritol, or their ethylene oxide, propylene oxide, or ε-caprolactone adducts (e.g., DPHA: dipentaerythritol hexaacrylate); acrylates of phenols such as phenoxy acrylate and phenoxyethyl acrylate, or their ethylene oxide or propylene oxide adducts; epoxy acrylates derived from glycidyl ethers such as trimethylolpropane triglycidyl ether, melamine acrylates, and / or methacrylates corresponding to the above-mentioned acrylates, etc. Among them, polyhydric acrylates or polyhydric methacrylates are preferred. For example, as trihydric acrylates or methacrylates, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, trimethylolpropane EO addition tri(meth)acrylate, glycerol PO addition tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, tetrafurfuryl alcohol oligo(meth)acrylate, ethyl carbitol oligo(meth)acrylate, 1,4-butanediol oligo(meth)acrylate, 1,6-hexanediol oligo(meth)acrylate, trimethylolpropane oligo(meth)acrylate, pentaerythritol oligo(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and the like can be cited. Examples of the trivalent or higher acrylates or methacrylates include tris(2-(meth)acryloyloxyethyl)phosphate, tris(2-(meth)acryloyloxypropyl)phosphate, tris(3-(meth)acryloyloxypropyl)phosphate, tris(3-(meth)acryloyl-2-hydroxyoxypropyl)phosphate, di(3-(meth)acryloyl-2-hydroxyoxypropyl)(2-(meth)acryloyloxyethyl)phosphate, and (3-(meth)acryloyl-2-hydroxyoxypropyl)di(2-(meth)acryloyloxyethyl)phosphate. These photosensitive (meth)acrylate compounds may be used alone or in combination of two or more.
[0108] The content of the component (E) when mixed is preferably 1% to 10% by mass, more preferably 3% to 8% by mass, based on 100% by mass of the nonvolatile component of the resin composition, from the viewpoint of promoting photocuring and suppressing stickiness when forming a cured product.
[0109] <(F) Organic solvent> The resin composition may further contain (F) an organic solvent. By containing (F) an organic solvent, the viscosity of the resin varnish may be adjusted. Examples of the (F) organic solvent include ketones such as methyl ethyl ketone and cyclohexanone; aromatic hydrocarbons such as toluene, xylene, and tetramethylbenzene; glycol ethers such as methyl cellosolve, butyl cellosolve, methyl carbitol, butyl carbitol, propylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol diethyl ether, and triethylene glycol monoethyl ether; esters such as ethyl acetate, butyl acetate, butyl cellosolve acetate, carbitol acetate (EDGAc: diethylene glycol monoethyl ether acetate), and ethyl diglycol acetate; aliphatic hydrocarbons such as octane and decane; petroleum solvents such as petroleum ether, naphtha, hydrogenated naphtha, and solvent naphtha. These organic solvents may be used alone or in combination of two or more. The content of the organic solvent when used may be appropriately adjusted from the perspective of the coating properties of the resin composition.
[0110] <(G) Other additives> The resin composition may further contain (G) other additives to the extent that the purpose of the present invention is not impaired. As (G) other additives, for example, various additives such as thermoplastic resins, organic fillers, microparticles of melamine, organic bentonite, etc., colorants such as phthalocyanine blue, phthalocyanine green, iodine green, diazo yellow, crystal violet, titanium oxide, carbon black, naphthalene black, polymerization inhibitors such as hydroquinone, phenothiazine, methylhydroquinone, hydroquinone monomethyl ether, catechol, pyrogallol, thickeners such as bentonite (Benton), montmorillonite, silicone-based, fluorine-based, vinyl resin-based defoamers, brominated epoxy compounds, acid-modified brominated epoxy compounds, antimony compounds, phosphorus-based compounds, aromatic condensed phosphates, halogen-containing condensed phosphates, and thermosetting resins such as phenolic curing agents and cyanate curing agents can be added.
[0111] <Manufacturing method> The resin composition can be manufactured by mixing the above components. During mixing, a mixing device such as a three-roll mill, a ball mill, a bead mill, a sand mill, or a stirring device such as a high-speed mixer or a planetary mixer can be used for mixing or stirring as needed. The resin composition can be obtained as a resin varnish by containing, for example, an organic solvent (F).
[0112] [2. Resin composition according to the second embodiment of the present invention] Hereinafter, the resin composition according to the second embodiment of the present invention will be described in detail.
[0113] The resin composition of the second embodiment of the present invention is a resin composition containing (A) a resin containing an ethylenically unsaturated group and a carboxyl group, (B) an inorganic filler having an average particle size of 0.5 μm or more, (C) an epoxy resin, and (D) a photopolymerization initiator. Regarding the resin composition of the second embodiment, the weighted average value S of the dissolution rate [nm / sec] of the component (A) in an alkaline solution based on the mass ratio is (A) Satisfies the following formula (I): 5≤S (A) ≤110···(I). The dissolution rate in an alkaline solution can be measured, for example, by the method described in the examples. As the alkaline solution, a developer generally used in development can be cited. In order to be able to compare the dissolution rates, a 1 mass % sodium carbonate aqueous solution having a constant pH (pH: 11.7) at 23° C. is preferably used as the alkaline solution. The temperature and pH of the alkaline solution may be appropriately changed as long as they do not have a significant effect on the dissolution rate.
[0114] By using the resin composition according to the second embodiment of the present invention, a cured product having excellent side corrosion resistance can be obtained.
[0115] <Component (A), component (B), component (C), and component (D)> The resin composition of the second embodiment contains the components (A), (B), (C), and (D), except that the component (A) may not contain the component (A-1), and the weighted average S of the dissolution rates of the component (A) is (A) Except for satisfying the formula (I), the components (A), (B), (C) and (D) are the same as those contained in the resin composition of the first embodiment. Thus, the same advantages as those of the resin composition of the first embodiment can be obtained.
[0116] The content, weight-average molecular weight and acid value of the (A) component are arbitrary, but preferably in the same range as the content, weight-average molecular weight and acid value of the (A) component described above in the first embodiment. Thus, the same advantages as those described in the item of the (A) component in the first embodiment can be obtained. The content, average particle size and specific surface area of the (B) component are arbitrary, but preferably in the same range as the content, average particle size and specific surface area of the (B) component described above in the first embodiment. Thus, the same advantages as those described in the item of the (B) component in the first embodiment can be obtained. The content, epoxy equivalent and weight-average molecular weight of the (C) component are arbitrary, but preferably in the same range as the content, epoxy equivalent and weight-average molecular weight of the (C) component described above in the first embodiment. Thus, the same advantages as those described in the item of the (C) component in the first embodiment can be obtained. The content of the (D) component is arbitrary, but preferably in the same range as the content of the (D) component described above in the first embodiment. Thus, the same advantages as those described in the item of the (D) component in the first embodiment can be obtained.
[0117] The weighted average S of the dissolution rate [nm / sec] of the component (A) contained in the resin composition of the present embodiment in the alkaline solution based on the mass ratio (A) The above formula (I) is satisfied. More specifically, the weighted average S of the dissolution rate of component (A) (A) It is usually 5 nm / sec or more, more preferably 6 nm / sec or more, further preferably 10 nm / sec or more, particularly preferably 15 nm / sec or more, and usually 110 nm / sec or less, preferably 100 nm / sec or less, more preferably 90 nm / sec or less, further preferably 80 nm / sec or less. (A) Being in the above range, the dissolution rate of the resin composition in the alkaline developer can be suppressed from becoming too slow or too fast. Therefore, it is possible to suppress the generation of excessively dissolved parts contrary to the intention and undissolved parts contrary to the intention locally. Therefore, the side erosion resistance can be improved, and preferably the side of the opening pattern can be made close to vertical relative to the layer plane.
[0118] The weighted average S of the dissolution rate of component (A) is taken as (A) The method of controlling the dissolution rate within the above range includes, for example, using a method in which the component (A) contains the component (A-1). However, for example, the type and amount of the component (A) other than the component (A-1) may be appropriately adjusted to obtain a weighted average value S of the dissolution rate of the component (A). (A) Control within the above range.
[0119] When a plurality of resins containing ethylenically unsaturated groups and carboxyl groups are used as component (A), it is more preferred that the dissolution rate [nm / sec] of each of the resins containing ethylenically unsaturated groups and carboxyl groups is within the above-mentioned range. As component (A) having a dissolution rate [nm / sec] within the range of 5 to 110, more preferably within the range of 5 to 100, there can be cited the resin solution (A-1a) obtained by the following Synthesis Example 1, the resin solution (A-1b) obtained by Synthesis Example 2, and "ZAR-2000" (acid-modified bisphenol-type epoxy acrylate: a reaction product of bisphenol A-type epoxy resin, acrylic acid, and succinic anhydride) manufactured by Nippon Kayaku Co., Ltd.
[0120] <Component (E), component (F), and component (G)> The resin composition of the present embodiment may further contain (E) reactive diluent, (F) organic solvent, (G) other additives as required. The components (E), (F) and (G) that may be contained in the resin composition of the second embodiment are the same as the components (E), (F) and (G) that may be contained in the resin composition of the first embodiment. Thus, the same advantages as those of the resin composition of the first embodiment can be obtained.
[0121] <Manufacturing method> The resin composition can be prepared by mixing the above components. During mixing, a mixing device such as a three-roll mill, a ball mill, a bead mill, a sand mill, or a stirring device such as a high-speed mixer or a planetary mixer can be used for mixing or stirring as needed. The resin composition can be obtained as a resin varnish by containing, for example, an organic solvent (F).
[0122] <Physical properties and uses of resin composition> After the resin composition of the first embodiment of the present invention or the resin composition of the second embodiment is photocured, the cured product obtained by heat curing it at 190°C for 90 minutes shows excellent side corrosion resistance. That is, an insulating layer and a solder mask layer with excellent side corrosion resistance can be provided. From the perspective of suppressing the shape of the positive cone, the value of undercut is preferably less than +10μm, more preferably less than +5μm, further preferably less than +4μm, and further more preferably less than +3μm. Here, the cross-sectional shape of the positive cone refers to a shape in which the diameter of the opening portion becomes narrower as it goes inward, specifically, a shape in which the bottom surface of the opening is narrower than the top surface of the opening. From the perspective of suppressing the shape of the inverted cone, the lower limit is preferably less than -5μm, more preferably less than -4μm, and further preferably less than -3μm. The value of undercut can be measured according to the method described in the following <Evaluation of developability, crack resistance and side corrosion resistance>.
[0123] In addition, the cured product obtained by photocuring the resin composition involved in the first embodiment or the second embodiment of the present invention and then thermally curing it at 190°C for 90 minutes has a tendency to show excellent developability. Therefore, there is usually no residue such as resin in the unexposed part. The minimum through-hole diameter without residue is preferably 100 μm or less, more preferably 90 μm or less, and further preferably 80 μm or less. The lower limit is not particularly limited and can be set to 1 μm or more. The evaluation of developability can be evaluated according to the method described in the following <Evaluation of developability, crack resistance and side erosion resistance>.
[0124] The cured product obtained by photocuring the resin composition involved in the first embodiment or the second embodiment of the present invention and then thermally curing it at 190°C for 90 minutes has a tendency to show characteristics such as a low average linear thermal expansion coefficient. That is, an insulating layer and a solder resist layer with a low average linear thermal expansion coefficient can be obtained. The average linear thermal expansion coefficient is preferably less than 45 ppm / °C, more preferably less than 40 ppm / °C, and further preferably less than 36 ppm / °C and less than 35 ppm / °C. The lower limit is not particularly limited and can be set to 10 ppm / °C or more. The average linear thermal expansion coefficient can be measured according to the method described in the following <Measurement of the average linear thermal expansion coefficient and the glass transition temperature>.
[0125] The cured product obtained by photocuring the resin composition involved in the first embodiment or the second embodiment of the present invention and then thermally curing it at 190°C for 90 minutes has a tendency to show characteristics such as a high glass transition temperature. That is, an insulating layer and a solder resist layer with a high glass transition temperature can be obtained. The glass transition temperature is preferably higher than 135°C, more preferably higher than 170°C, and further preferably higher than 180°C. The upper limit is not particularly limited and can be set to 300°C or less. The glass transition temperature can be measured according to the method described in the following <Measurement of the average linear thermal expansion coefficient and the glass transition temperature>.
[0126] The cured product obtained by photocuring the resin composition involved in the first embodiment or the second embodiment of the present invention and then thermally curing it at 190°C for 90 minutes shows excellent crack resistance. That is, an insulating layer and a solder resist layer with excellent crack resistance can be obtained. Even if a thermal cycle test of heating and cooling between -65°C and 150°C is repeated 500 times, no cracks or peeling are observed. The evaluation of crack resistance can be evaluated according to the method described in the following <Evaluation of developability, crack resistance and side corrosion resistance>.
[0127] The use of the resin composition involved in the first embodiment or the second embodiment of the present invention is not particularly limited, and can be used for a wide range of uses that require resin compositions, such as photosensitive films, photosensitive films with supports, insulating resin sheets such as prepregs, circuit substrates (laminated board uses, multilayer printed wiring board uses, etc.), solder resists, bottom filling materials, chip bonding materials, semiconductor sealing materials, buried hole resins, and component embedding resins. Among them, it can be suitably used as: a resin composition for an insulating layer of a printed wiring board (a printed wiring board using a cured product of the resin composition as an insulating layer), a resin composition for an interlayer insulating layer (a printed wiring board using a cured product of the resin composition as an interlayer insulating layer), a resin composition for plating formation (a printed wiring board having a plating layer formed on a cured product of the resin composition), and a resin composition for a solder resist layer (a printed wiring board using a cured product of the resin composition as a solder resist).
[0128] [Photosensitive film] By using the resin composition involved in the first embodiment or the second embodiment of the present invention, a photosensitive film containing the resin composition can be obtained. For example, the resin composition is applied to a supporting substrate in a resin varnish state, and the organic solvent is dried to form a resin composition layer to make a photosensitive film. In addition, the photosensitive film pre-formed on the support body can also be laminated on the supporting substrate for use. The photosensitive film can be laminated on various supporting substrates. As the supporting substrate, substrates such as glass epoxy substrates, metal substrates, polyester substrates, polyimide substrates, BT resin substrates, and thermosetting polyphenylene ether substrates can be mainly listed.
[0129] [Photosensitive film with support] The resin composition involved in the first embodiment or the second embodiment of the present invention can be used in the form of a photosensitive film with a support in which a resin composition layer is formed on a support. That is, the photosensitive film with a support includes a support and a resin composition layer formed from the resin composition of the present invention and disposed on the support.
[0130] Examples of the support include polyethylene terephthalate films, polyethylene naphthalate films, polypropylene films, polyethylene films, polyvinyl alcohol films, and triacetyl acetate films, and polyethylene terephthalate films are particularly preferred.
[0131] As commercially available supports, for example, there can be cited: products named "ALPHAN MA-410" and "E-200C" manufactured by Oji Paper Co., Ltd., polypropylene films manufactured by Shin-Etsu Film Co., Ltd., polyethylene terephthalate films of the PS series such as the product named "PS-25" manufactured by Teijin Co., Ltd., etc., but are not limited to these. For these supports, in order to facilitate the removal of the resin composition layer, it is preferred to coat a release agent such as a silicone coating agent on the surface. The thickness of the support is preferably in the range of 5μm to 50μm, and more preferably in the range of 10μm to 25μm. By making the thickness greater than 5μm, damage to the support can be suppressed when the support is peeled off before development; by making the thickness less than 50μm, the resolution when exposing from above the support can be improved. In addition, a support with a low white spot (fish eye) is preferred. The white spots referred to herein are white spots formed when foreign matter, undissolved matter, oxidative degradation products, etc. of the material enter the film when the material is produced by hot melting, kneading, extrusion, biaxial stretching, casting, etc.
[0132] In addition, in order to reduce the scattering of light when exposed to active energy rays such as ultraviolet rays, the support is preferably a material with excellent transparency. Specifically, the support is preferably a material with a turbidity (haze standardized according to JIS K6714) of 0.1 to 5 as a transparency index. Furthermore, the resin composition layer may also be protected by a protective film.
[0133] By protecting the resin composition layer side of the photosensitive film with a support with a protective film, it is possible to prevent dust from adhering to the surface of the resin composition layer or scratches. As a protective film, a film made of the same material as the above-mentioned support can be used. The thickness of the protective film is not particularly limited, preferably in the range of 1 μm to 40 μm, more preferably in the range of 5 μm to 30 μm, and further preferably in the range of 10 μm to 30 μm. By making the thickness more than 1 μm, the operability of the protective film can be improved, and by making the thickness less than 40 μm, there is a tendency for cheapness to become good. It should be noted that the protective film is preferably a protective film that makes the adhesion between the resin composition layer and the protective film smaller relative to the adhesion between the resin composition layer and the support.
[0134] The photosensitive film with a support of the present invention can be manufactured as follows according to a method known to those skilled in the art: for example, a resin varnish is prepared by dissolving the resin composition of the present invention in an organic solvent, the resin varnish is applied on the support, and the organic solvent is dried by heating or hot air blowing to form a resin composition layer. Specifically, first, after completely removing the bubbles in the resin composition by a vacuum degassing method, the resin composition is applied to the support, the solvent is removed by a hot air furnace or a far infrared furnace, and it is dried, and then a protective film is laminated on the obtained resin composition layer as needed, thereby manufacturing a photosensitive film with a support. The specific drying conditions vary depending on the curability of the resin composition and the amount of organic solvent in the resin varnish. In a resin varnish containing 30% to 60% by mass of an organic solvent, it can be dried at 80°C to 120°C for 3 minutes to 13 minutes. The amount of residual organic solvent in the resin composition layer is preferably 5% by mass or less, and more preferably 2% by mass or less relative to the total amount of the resin composition layer from the perspective of preventing the diffusion of the organic solvent in the subsequent process. Those skilled in the art can appropriately set appropriate drying conditions through simple experiments. From the perspective of improving the handleability and suppressing the reduction of the sensitivity and resolution inside the resin composition layer, the thickness of the resin composition layer is preferably set to a range of 5 μm to 500 μm, more preferably set to a range of 10 μm to 200 μm, further preferably set to a range of 15 μm to 150 μm, further more preferably set to a range of 20 μm to 100 μm, and particularly more preferably set to a range of 20 μm to 60 μm.
[0135] As the coating method of resin composition, for example, gravure coating method, micro gravure coating method, reverse coating (reverse coating) method, contact reverse coating (kiss reverse coating) method, die coating (die coating) method, slot die method, lip coating (lip coating) method, comma coating (comma coating) method, blade coating (blade coating) method, roller coating method, knife coating (knife coating) method, curtain coating (curtain coating) method, closed chamber (chamber) gravure coating method, slot nozzle type (slot orifice) method, spray coating method, dip coating method, etc. The resin composition can be coated in fractions, or it can be coated once, and it can also be coated in combination of multiple different methods. Among them, the roller coating method with excellent coating uniformity is preferred. In addition, in order to avoid foreign matter from mixing, it is preferred to implement the coating process in an environment where foreign matter such as a clean room is less produced.
[0136] [Printed wiring board] The printed wiring board of the present invention includes an insulating layer formed of a cured product of the resin composition according to the first embodiment or the second embodiment of the present invention. The insulating layer is preferably used as a solder resist layer.
[0137] Specifically, the printed wiring board of the present invention can be produced using the above-mentioned photosensitive film or the photosensitive film with a support. Hereinafter, the case where the insulating layer is a solder resist layer will be described.
[0138] <Coating and drying process> The resin composition is directly applied to the circuit board in the form of a resin varnish, and the organic solvent is dried to form a photosensitive film on the circuit board.
[0139] Examples of the circuit substrate include glass epoxy substrates, metal substrates, polyester substrates, polyimide substrates, BT resin substrates, and thermosetting polyphenylene ether substrates. It should be noted that the circuit substrate referred to herein refers to a substrate having a patterned conductor layer (circuit) formed on one or both sides of the substrate. In addition, in a multilayer printed wiring board formed by alternately stacking conductor layers and insulating layers, a substrate having a patterned conductor layer (circuit) formed on one or both sides of the outermost layer of the multilayer printed wiring board is also included in the circuit substrate referred to herein. It should be noted that the surface of the conductor layer may be pre-roughened by blackening, copper etching, or the like.
[0140] As a coating method, full-plate printing based on screen printing is usually used, but any other means can also be used as long as it is a coating method that can be evenly coated. For example, spray coating, hot melt coating, rod coating, coating, scraper coating, blade coating, air knife coating, curtain flow coating, roller coating, gravure coating, offset printing, dip coating, brush coating, and other common coating methods can all be used. After coating, dry it using a hot air furnace or a far infrared furnace as needed. The drying conditions are preferably dried at 80°C to 120°C for 3 minutes to 13 minutes. Such operation can form a photosensitive film on the circuit substrate.
[0141] <Lamination process> In addition, when using a photosensitive film with a support, a vacuum laminator is used to laminate the resin composition layer side to one or both sides of the circuit substrate. In the lamination process, when the photosensitive film with a support has a protective film, after removing the protective film, the photosensitive film with a support and the circuit substrate are preheated as needed, and the resin composition layer is pressed and heated while being bonded to the circuit substrate. For the photosensitive film with a support, a method of laminating on the circuit substrate under reduced pressure by a vacuum lamination method can be suitably used.
[0142] The conditions of the lamination process are not particularly limited. For example, the preferred conditions are: the pressing temperature (lamination temperature) is preferably set to 70° C. to 140° C., and the pressing pressure is preferably set to 1 kgf / cm 2 ~11kgf / cm 2 (9.8×10 in SI units 4 N / m 2 ~107.9×10 4 N / m 2 ), the pressing time is preferably set to 5 seconds to 300 seconds, and the lamination is performed under reduced pressure with the air pressure set to 20 mmHg (26.7 hPa in SI units) or less. In addition, the lamination process can be a batch type or a continuous type using a roller. The vacuum lamination method can be performed using a commercially available vacuum laminator. As commercially available vacuum laminators, for example, there can be listed: a vacuum applicator manufactured by Nikko-Materials, a vacuum pressurized laminator manufactured by Meiki Manufacturing Co., Ltd., a roller dry coater manufactured by Hitachi Industries, a vacuum laminator manufactured by Hitachi AIC, etc. Such operation can form a photosensitive film on a circuit substrate.
[0143] <Exposure process> After a photosensitive film is provided on the circuit board by a coating and drying process or a lamination process, an exposure process is performed to photocure the resin composition layer in the irradiated part by irradiating a predetermined part of the resin composition layer with activating rays through a mask pattern. Examples of activating rays include ultraviolet rays, visible rays, electron beams, and X-rays, and ultraviolet rays are particularly preferred. The irradiation amount of ultraviolet rays is about 10 mJ / cm 2 ~1000mJ / cm 2 The exposure method includes a contact exposure method in which the mask pattern is brought into close contact with the printed wiring board, and a non-contact exposure method in which parallel light is used for exposure in a non-closed state. Any of the above methods can be used. In addition, when a support is present on the resin composition layer, the exposure can be carried out from the support, or the exposure can be carried out after the support is peeled off.
[0144] Since the solder resist uses the resin composition of the present invention, it has excellent developability. Therefore, as an exposure pattern in a mask pattern, for example, a ratio (L / S) of a circuit width (line width: L) to a width between circuits (line spacing: S) of 100 μm / 100 μm or less (i.e., wiring spacing of 200 μm or less), L / S=80 μm / 80 μm or less (wiring spacing of 160 μm or less), L / S=70 μm / 70 μm or less (wiring spacing of 140 μm or less), L / S=60 μm / 60 μm or less (wiring spacing of 120 μm or less) can be used. It should be noted that the spacing does not need to be the same in the overall range of the circuit substrate.
[0145] <Development process> When a support is present on the resin composition layer after the exposure step, the support is removed, and then the unphotocured portion (unexposed portion) is removed by wet development and developed, thereby forming a pattern.
[0146] In the case of the wet development, an alkaline solution is usually used as a developer, and a development process using an alkaline aqueous solution is preferred. In addition, as a developing method, a known method such as spraying, shaking immersion, brushing, scraping, etc. can be appropriately used.
[0147] As the alkaline solution used as the developer, for example, there can be listed: alkali metal hydroxides such as lithium hydroxide, sodium hydroxide, potassium hydroxide, carbonates or bicarbonates such as sodium carbonate and sodium bicarbonate, alkali metal phosphates such as sodium phosphate and potassium phosphate, aqueous solutions of alkali metal pyrophosphates such as sodium pyrophosphate and potassium pyrophosphate, or aqueous solutions of organic bases such as tetraalkylammonium hydroxide that do not contain metal ions. From the point of view that it does not contain metal ions and does not affect the semiconductor chip, an aqueous solution of tetramethylammonium hydroxide (TMAH) is preferred. In these alkaline developers, in order to improve the development effect, a surfactant, a defoamer, etc. can be contained in the developer. The pH value of the alkaline solution is preferably in the range of 8 to 13, more preferably in the range of 9 to 12, and further preferably in the range of 10 to 12. In addition, the alkali concentration of the alkaline developer is preferably 0.1% by mass to 10% by mass. The temperature of the alkaline developer can be appropriately selected according to the developability of the resin composition layer, usually room temperature, preferably 20°C to 50°C.
[0148] Examples of the organic solvent used as the developer include acetone, ethyl acetate, alkoxyethanol having an alkoxy group having 1 to 4 carbon atoms, ethanol, isopropyl alcohol, butanol, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, and diethylene glycol monobutyl ether.
[0149] The concentration of such an organic solvent is preferably 2% to 90% by mass relative to the total amount of the developer. In addition, the temperature of such an organic solvent can be adjusted according to the developability. Furthermore, such an organic solvent can be used alone or in combination of two or more. Examples of organic solvent-based developers used alone include: 1,1,1-trichloroethane, N-methylpyrrolidone, N,N-dimethylformamide, cyclohexanone, methyl isobutyl ketone, and γ-butyrolactone.
[0150] In pattern formation, two or more of the above-mentioned developing methods can be used simultaneously as needed. The developing methods include dipping, spinning immersion, spraying, high-pressure spraying, brushing, scraping, etc. The high-pressure spraying method is preferred because it improves the resolution. When the spraying method is used, the spray pressure is preferably 0.05MPa to 0.3MPa.
[0151] According to the resin composition according to the first embodiment or the second embodiment, the occurrence of side etching can be effectively suppressed in the aforementioned development step.
[0152] <Thermal Curing (Post-baking) Process> After the development process is completed, a thermal curing (post-baking) process is performed to form a solder resist layer. As the post-baking process, an ultraviolet irradiation process using a high-pressure mercury lamp or a heating process using a clean oven can be listed. When irradiating ultraviolet rays, the irradiation amount can be adjusted as needed, for example, 0.05 J / cm 2 ~10J / cm 2 In addition, the heating conditions can be appropriately selected according to the type and content of the resin component in the resin composition, but are preferably selected in the range of 20 minutes to 180 minutes at 150°C to 220°C, and more preferably in the range of 30 minutes to 120 minutes at 160°C to 200°C.
[0153] <Other Process> For the printed wiring board, after forming the solder resist layer, a hole opening step and a desmear step may be further included. These steps can be carried out according to various methods known to those skilled in the art used in the production of the printed wiring board.
[0154] After forming the solder mask, the solder mask formed on the circuit substrate is subjected to a perforation process to form through holes and through holes as required. The perforation process can be carried out by known methods such as a drill, a laser, and a plasma and by combining these methods as required, preferably by a perforation process performed by lasers such as a carbon dioxide laser and a YAG laser.
[0155] The desmearing process is a process for performing desmearing treatment. Resin residue (smearing) is usually attached to the inside of the opening formed in the hole-forming process. This smearing can cause poor electrical connection, so the process of removing the smearing (desmearing treatment) is implemented in this process.
[0156] The desmear treatment can be performed by dry desmear treatment, wet desmear treatment or a combination of the two.
[0157] As dry desmear treatment, for example, desmear treatment using plasma can be cited. Desmear treatment using plasma can be implemented using a commercially available plasma desmear treatment device. Among the commercially available plasma desmear treatment devices, examples suitable for the manufacture of printed wiring boards include: a microwave plasma device manufactured by NISSIN, a normal pressure plasma etching device manufactured by Sekisui Chemical Co., Ltd., and the like.
[0158] As wet desmear treatment, for example, desmear treatment using an oxidant solution can be cited. When the desmear treatment is performed using an oxidant solution, it is preferred to sequentially perform swelling treatment using a swelling solution, oxidation treatment using an oxidant solution, and neutralization treatment using a neutralizing solution. As swelling solution, for example, "Swelling Dip Securiganth P" and "Swelling Dip Securiganth SBU" manufactured by ATOTECH JAPAN can be cited. The swelling treatment is preferably performed by immersing a substrate having through holes formed therein, etc. in a swelling solution heated to 60°C to 80°C for 5 to 10 minutes. As an oxidant solution, an alkaline permanganate aqueous solution is preferred, and for example, a solution in which potassium permanganate or sodium permanganate is dissolved in an aqueous sodium hydroxide solution can be cited. The oxidation treatment using an oxidant solution is preferably performed by immersing the substrate after the swelling treatment in an oxidant solution heated to 60°C to 80°C for 10 to 30 minutes. As commercially available products of alkaline permanganate aqueous solution, for example, "Concentrate Compact CP" and "Dosing Solution Securiganth P" manufactured by ATOTECH JAPAN Co., Ltd. are listed. The neutralization treatment using the neutralizing solution is preferably performed by immersing the substrate after the oxidation treatment in the neutralizing solution at 30°C to 50°C for 3 minutes to 10 minutes. As the neutralizing solution, an acidic aqueous solution is preferably used, and as commercially available products, for example, "Reduction Solution Securiganth P" manufactured by ATOTECH JAPAN Co., Ltd. is listed.
[0159] When the dry desmear treatment and the wet desmear treatment are performed in combination, the dry desmear treatment may be performed first, or the wet desmear treatment may be performed first.
[0160] Even when the insulating layer is used as an interlayer insulating layer, the same process as the solder resist layer can be performed, and the hole opening process, the desmear process and the plating process can be performed after the thermal curing process.
[0161] The plating process is a process for forming a conductor layer on the insulating layer. The conductor layer can be formed by combining electroless plating and electrolytic plating. In addition, a plating resist (plating resist) having a pattern opposite to that of the conductor layer can be formed, and the conductor layer can be formed only by electroless plating. As a method for subsequent pattern formation, for example, a subtractive method, a semi-additive method, etc. known to those skilled in the art can be used.
[0162] [Semiconductor devices] The semiconductor device of the present invention includes a printed wiring board. The semiconductor device of the present invention can be manufactured using the printed wiring board of the present invention.
[0163] Examples of the semiconductor device include various semiconductor devices used in electrical products (eg, computers, mobile phones, digital cameras, and televisions) and vehicles (eg, motorcycles, cars, trains, ships, and aircraft).
[0164] The semiconductor device of the present invention can be manufactured by mounting a component (semiconductor chip) on a conductive portion of a printed wiring board. "Conductive portion" refers to "a portion of a printed wiring board that conducts electrical signals", and its location can be on the surface or in an embedded portion. In addition, the semiconductor chip is not particularly limited as long as it is an electrical circuit element made of semiconductor.
[0165] Regarding the method for mounting the semiconductor chip when manufacturing the semiconductor device of the present invention, there is no particular limitation as long as the semiconductor chip can function effectively, and specific examples include a wire bonding mounting method, a flip chip mounting method, a mounting method using a solderless build-up layer (BBUL), a mounting method using an anisotropic conductive film (ACF), a mounting method using a non-conductive film (NCF), etc. Here, "a mounting method using a solderless build-up layer (BBUL)" refers to "a mounting method in which a semiconductor chip is directly embedded in a recess of a printed wiring board to connect the semiconductor chip to the wiring on the printed wiring board". Example
[0166] The present invention will be specifically described below by way of examples, but the present invention is not limited to these examples. It should be noted that in the following description, "parts" and "%" indicating amounts represent "parts by mass" and "mass %" respectively, unless otherwise expressly stated.
[0167] (Synthesis Example 1: Synthesis of Resin Solution (A-1a)) 162 parts of epoxy resin A (1,1'-bis(2,7-diepoxypropoxynaphthyl)methane, epoxy equivalent 162, "EXA-4700" manufactured by Dainippon Ink & Chemicals Co., Ltd.) containing a naphthalene skeleton represented by the following formula (8) were placed in a flask equipped with a gas inlet tube, a stirring device, a cooling tube and a thermometer, 340 parts of carbitol acetate were added, heated and dissolved, and 0.46 parts of hydroquinone and 1 part of triphenylphosphine were added. The mixture was heated to 95-105°C, 72 parts of acrylic acid were slowly added dropwise, and the reaction was carried out for 16 hours. The reaction product was cooled to 80-90°C, 80 parts of tetrahydrophthalic anhydride were added, the reaction was carried out for 8 hours, and the reaction was cooled. In this way, a resin solution having an acid value of 90 mgKOH / g of solid matter was obtained (non-volatile matter 70%, hereinafter referred to as "resin solution (A-1a)").
[0168] [Chemistry 7]
[0169] It was confirmed that the resin solution (A-1a) contained at least a resin represented by the following formula (9).
[0170] [Chemistry 8]
[0171] (Synthesis Example 2: Synthesis of Resin Solution (A-1b)) In Synthesis Example 1, the epoxy resin A containing a naphthalene skeleton was replaced with 325 parts of a naphthol aralkyl type epoxy resin B (epoxy equivalent 325, "ESN-475V" manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd.) represented by the following formula (10). Except for the above matters, the same operation as in Synthesis Example 1 was performed. In this way, a resin solution having an acid value of 60 mgKOH / g of solid matter was obtained (non-volatile content 70%, hereinafter referred to as "resin solution (A-1b)").
[0172] [Chemistry 9] (Z is a glycidyl group (G) or a hydrocarbon group (R7) having 1 to 8 carbon atoms, and the ratio of R7 / G is 0.05 to 2.0. In addition, n represents a number of 1 to 6 as an average value.)
[0173] It was confirmed that the resin solution (A-1b) contained at least a resin having a structure represented by the following formula (11).
[0174] [Chemistry 10]
[0175] <Examples 1 to 7, Comparative Examples 1 and 2> The components were mixed in the proportions shown in Table 1 below, and a resin varnish was prepared using a high-speed rotary mixer. Next, a PET film ("Lumirror T6AM" manufactured by Toray Industries, Ltd., thickness 38 μm, softening point 130°C, "release PET") that had been subjected to release treatment with an alkyd resin-based release agent ("AL-5" manufactured by Lintec) was prepared as a support. The prepared resin varnish was evenly applied to the surface of the release PET treated with the alkyd resin-based release agent using a die coater so that the thickness of the resin composition layer after drying was 40 μm, and dried at 80°C to 110°C for 6.5 minutes to obtain a photosensitive film with a support having a resin composition layer on the release PET.
[0176] The measurement method and evaluation method in the evaluation of physical properties are described.
[0177] <Evaluation of dissolution rate of resin composition> Resin solution (A-1a), resin solution (A-1b) and the following resins ZFR-1491H, ZAR-2000 and ZCR-1569H are respectively added to propylene glycol monomethyl ether acetate (PGMEAc) to prepare a solution with a non-volatile component of 35% by weight. The solution is applied to a silicon wafer and spin-coated to obtain a coating film. Then, the coating film is dried at 120°C for 3 minutes to form a resin film with a thickness of about 2 μm. The film thickness of the resin film is measured using a stylus film thickness meter (manufactured by Tokyo Seimitsu Co., Ltd., "SURFCOM 130A"). Then, the resin film is immersed in a 1% by mass sodium carbonate aqueous solution (pH: 11.7) as an alkaline solution at 23°C together with the silicon wafer. Then, the disappearance time until the resin film disappears is measured. The disappearance of the resin film is confirmed by visually observing the disappearance of interference fringes caused by reflected light on the surface of the resin film. Therefore, the disappearance time is the time from the moment when the resin film is immersed in the alkaline solution to the moment when the disappearance is confirmed. Then, for each resin film, the dissolution rate [nm / sec] representing the amount of reduction in the thickness [nm] of the resin film per 1 second is calculated. For the resin film that was not found to be dissolved even after immersion for 30 minutes, the dissolution rate was set to 1nm / sec. The results are as follows. (A-1) Ingredients: A-1a: 100nm / sec A-1b: 6nm / sec (A-2) Ingredients: ZFR-1491H: 131nm / sec ZAR-2000: 39nm / sec ZCR-1569H: 1nm / sec For each of the Examples and Comparative Examples, the weighted average S of the dissolution rate [nm / sec] of the component (A) in the alkaline solution based on the mass ratio was calculated using the following formula (IV): (A) . S (A) =Σ{s(A)×R (A)}···(IV) In the above formula (IV), s(A) is the dissolution rate of each component (A) in the alkaline solution. (A) It is the mass ratio of each resin (A) when the non-volatile component in (A) component is 100 mass %.
[0178] <Evaluation of developability, crack resistance, and side corrosion resistance> (Formation of Evaluation Laminated Body) For the copper layer of the glass epoxy substrate (copper-clad laminate) in which a circuit with a copper layer of 18 μm in thickness is patterned, roughening is performed by treatment with a surface treatment agent (CZ8100, manufactured by MEC) containing an organic acid. Next, the resin composition layer of the photosensitive film with a support obtained by Examples 1 to 7 and Comparative Examples 1 to 2 is arranged in contact with the surface of the copper circuit, and a vacuum laminator (Nikko-Materials, VP160) is used for crimping to form a laminate in which the copper-clad laminate, the resin composition layer and the support are sequentially laminated. The crimping conditions are set to 30 seconds for vacuuming time, 80°C for crimping temperature, 0.7MPa for crimping pressure, and 30 seconds for pressing time. The laminate is left to stand at room temperature for more than 30 minutes, and is exposed to ultraviolet light from the support side of the laminate using a quartz glass mask and a pattern forming device having an exposure pattern for forming a circular hole. The quartz glass mask used is provided with a pattern of 6 types of circular holes with diameters of 50μm / 60μm / 70μm / 80μm / 90μm / 100μm. After standing at room temperature for 30 minutes, the support is peeled off from the aforementioned laminate. On the entire surface of the resin composition layer on the laminate, a 1 mass % sodium carbonate aqueous solution at 30°C is used as an alkaline developer and sprayed for 2 minutes at a spray pressure of 0.2MPa. As a result, in Examples 1 to 7 and Comparative Example 2, the circular holes are partially dissolved (eluted) to form through holes in the resin composition layer. On the other hand, in Comparative Example 1, no through holes are formed. After spray development, 1J / cm 2The resin composition layer was cured by ultraviolet irradiation and further subjected to a heating treatment at 180°C for 30 minutes. In this way, the resin composition layer was cured, and in Examples 1 to 7 and Comparative Example 2, a laminate for evaluation having an insulating layer on a copper-clad laminate was obtained, wherein the insulating layer had an opening (through hole). In Comparative Example 1, a laminate for evaluation having an insulating layer without a through hole formed on a copper-clad laminate was obtained.
[0179] (Evaluation of Development Property) The through holes formed in the evaluation laminate were observed by SEM (magnification 1000 times), and the minimum through hole diameter without residue was determined among a total of 6 types of through holes. When the opening (through hole) could not be confirmed in the evaluation laminate, it was judged that the minimum through hole diameter could not be determined and the evaluation was "×".
[0180] (Evaluation of crack resistance) The following test was conducted: a treatment using a thermal cycle was repeated 500 times, wherein the evaluation laminate was exposed to an atmosphere of -65°C for 15 minutes, then heated at a heating rate of 180°C / min, and then exposed to an atmosphere of 175°C for 15 minutes, then cooled at a cooling rate of 180°C / min. After the test, the degree of cracks and peeling of the evaluation laminate was observed using an optical microscope (manufactured by Nikon Corporation, "ECLIPSE LV100ND"), and evaluated according to the following criteria. ○: Neither cracks nor peeling were observed. ×: One or both of cracks and peeling were observed.
[0181] (Evaluation of side corrosion resistance) Figure 1 : is a cross-sectional view of the evaluation laminate used in the examples. Figure 1 As shown, in the evaluation laminate 100, the insulating layer 120 formed of the cured product of the resin composition provided on the copper-clad laminate 110 has a through hole 130 with a diameter of 100 μm as an opening. The insulating layer 120 of the evaluation laminate 100 was cut along a plane passing through the central axis of the through hole 130, and the cross section was observed by SEM to measure the Figure 1 The radius (x [μm]) of the opening top surface 140 and the radius (y [μm]) of the opening bottom surface 150 are shown, and the difference xy [μm] is obtained, and the side erosion value [μm] is calculated from this. When no opening (through hole) can be confirmed in the evaluation laminate, it is judged that the side erosion value cannot be calculated and the evaluation is "×".
[0182] <Measurement of average linear thermal expansion coefficient and glass transition temperature> (Formation of Cured Material for Evaluation) The resin composition layer of the photosensitive film with support obtained in Examples and Comparative Examples was subjected to a 100 mJ / cm 2 The resin composition layer was exposed to ultraviolet light to be photocured. Then, a 1% by mass sodium carbonate aqueous solution at 30°C as an alkaline developer was sprayed on the entire surface of the resin composition layer at a spray pressure of 0.2 MPa for 2 minutes. After the spray development, a 1 J / cm 2 The substrate was irradiated with ultraviolet rays and further heated at 190° C. for 90 minutes to form a cured product. The support was then peeled off to form a cured product for evaluation.
[0183] (Determination of average linear thermal expansion coefficient) The cured product for evaluation was cut into test pieces with a width of 5 mm and a length of 15 mm, and a thermomechanical analysis was performed using a thermomechanical analyzer (ThermoPlus TMA8310, manufactured by Rigaku Corporation) using a tensile load method. After the test piece was assembled in the aforementioned device, it was continuously measured twice under the measurement conditions of a load of 1 g and a heating rate of 5°C / min. The average linear thermal expansion coefficient (ppm / °C) from 25°C to 150°C in the second measurement was calculated.
[0184] (Determination of glass transition temperature) The cured product for evaluation was cut into test pieces with a width of about 5 mm and a length of about 15 mm, and a dynamic viscoelasticity measuring device (EXSTAR6000, manufactured by SII Nano Technology) was used to perform thermomechanical analysis using a tensile load method. After the test piece was assembled in the aforementioned device, the measurement was performed under the measurement conditions of a load of 200 mN and a heating rate of 2°C / min. The peak value of tanδ obtained was calculated as the glass transition temperature (°C).
[0185] [Table 1] (Table 1)
[0186] The ingredients used are described below. (A) Ingredients: (A-1)Ingredients A-1a: Resin solution synthesized in Synthesis Example 1 (A-1a) A-1b: Resin solution synthesized in Synthesis Example 2 (A-1b) (A-2)Ingredients ·ZFR-1491H: Bisphenol F epoxy acrylate (manufactured by Nippon Kayaku Co., Ltd., acid value 99 mgKOH / g, non-volatile content concentration 70%) ZAR-2000: Bisphenol A epoxy acrylate (manufactured by Nippon Kayaku Co., Ltd., acid value 99 mgKOH / g, non-volatile content 70%) ·ZCR-1569H: Biphenyl epoxy acrylate (manufactured by Nippon Kayaku Co., Ltd., acid value 98 mgKOH / g, non-volatile content concentration 70%) (B) Ingredients: SC2050: fused silica (manufactured by Yaduma Co., Ltd., average particle size 0.5 μm, specific surface area 5.9 m 2 / g) 100 parts by mass, and surface treated with 0.5 parts by mass of aminosilane (KBM573 manufactured by Shin-Etsu Chemical Co., Ltd.) (C) NC3000H: Biphenyl type epoxy resin (manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent weight about 272) 1031S: Tetrahydroxyphenylethane type epoxy resin (manufactured by Mitsubishi Chemical Corporation, epoxy equivalent weight about 200) (D) Ingredients: ·Irgacure TPO: Bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide) (manufactured by BASF) (E) Ingredients: DPHA: Dipentaerythritol hexaacrylate (manufactured by Nippon Kayaku Co., Ltd., acryloyl equivalent weight about 96) (F)Ingredients: EDGAc: Diethylene glycol monoethyl ether acetate MEK: Methyl Ethyl Ketone Content of component (B): Content of component (B) when the nonvolatile component of the resin composition is 100% by mass [% by mass] · Weighted average of dissolution rate S (A) : Weighted average of the dissolution rate [nm / sec] of component (A) in alkaline solution based on the mass ratio Side erosion value: Side erosion value in a through hole with a diameter of 100 μm [μm]
[0187] <Discussion> As can be seen from the results of Table 1 above, Examples 1 to 7 using the resin composition of the present invention have excellent side erosion resistance. It is believed that the reason is that the (A-1) component itself can be dissolved in an alkaline solution (e.g., an alkaline developer) at a dissolution rate within an appropriate range, and when the resin composition containing the (A-1) component is developed with an alkaline developer, it is possible to suppress the local generation of excessively dissolved portions contrary to the intention and insoluble portions contrary to the intention in the resin composition. As one of the reasons, it is speculated that even if the resin composition contains components (C) to (E), the (A-1) component can be well blended, and the uneven composition in the resin composition can be suppressed.
[0188] It is also known that for Examples 1 to 7, compared with Comparative Examples 1 and 2, it has good developability, heat resistance, mechanical strength and crack resistance. Specifically, it is also known that for Examples 1 to 7, the average linear thermal expansion coefficient is low and the glass transition temperature is high. It is believed that the reason is that when the (A-1) component uses a resin containing a naphthalene skeleton, the rigidity of the molecule usually becomes higher, so the activity of the molecules in the resin composition is suppressed, as a result, the glass transition temperature of the cured product of the resin composition becomes higher, and the average linear thermal expansion coefficient of the cured product is further reduced. Further, it is believed that through the effect of the (A-1) component, the tolerance of the cured product to the internal stress generated by thermal expansion or thermal contraction is usually improved, so the breakage of the cured product caused by temperature changes can be suppressed.
[0189] Furthermore, it can be seen from Examples 4 to 6 that the weighted average S of the dissolution rates of Examples 1 to 4 and 7 can be adjusted by using the components (A-1) and (A-2) in combination. (A) , average linear thermal expansion coefficient and glass transition temperature. Further, according to the comparison between Examples 1 to 5 and Examples 6 and 7, it can be seen that by using the resin solution (A-1a), the minimum through-hole diameter can be controlled to a smaller value, and the side etching value tends to be maintained at a positive value even in the range of +10μm to -5μm. On the other hand, by using the resin solution (A-1b), the weighted average value S of the dissolution rate can be increased compared to the case of using the resin solution (A-1a) alone. (A) , thereby making the side surfaces of the opening pattern nearly perpendicular to the layer plane.
[0190] On the other hand, since the component (A-1) was not used in Comparative Examples 1 and 2, the side corrosion resistance was poor. This is considered to be because the dissolution rate of the component (A) was too low or too high.
[0191] In each example, even when the component (E) was not contained, it was confirmed that the same results as those of the above-mentioned examples were obtained, although the degree of difference was different.
[0192] Explanation of symbols 100 Evaluation laminate 110 Copper Clad Laminated Board 120 Insulation layer 130 Through hole 140 Open top 150 Open bottom.
Claims
1. A resin composition comprising the following components: (A) a resin containing an ethylenically unsaturated group and a carboxyl group, (B) an inorganic filler having an average particle size of 0.5 μm or more, (C) epoxy resin, and (D) a photopolymerization initiator, in, The component (A) comprises: (A-1) a resin having a naphthalene skeleton, (A-1) is a resin having a structure represented by the following formula (1), In formula (1), R 1 and R 2 Each independently represents an alkylene group which may have a substituent, X represents an arylene group which may have a substituent, and the arylene group is phenylene, anthracene, or phenanthrenyl. R' each independently represents an organic group containing an ethylenically unsaturated group and a carboxyl group, a represents 0 or 1, s represents 0 or 1, t represents 0 or 1, wherein, with respect to s and t, s+t is not 0, c represents an integer of 1-6.
2. The resin composition according to claim 1, wherein The component (A-1) is a naphthol aralkyl type resin.
3. The resin composition according to claim 1 or 2, wherein When the nonvolatile matter in the component (A) is 100% by mass, the content of the component (A-1) is 5% by mass or more.
4. The resin composition according to claim 1 or 2, wherein When the nonvolatile matter in the resin composition is 100 mass %, the content of the component (A) is 10 mass % or more and 30 mass % or less.
5. The resin composition according to claim 1 or 2, wherein When the nonvolatile matter in the resin composition is 100% by mass, the content of the component (B) is 60% by mass or more.
6. The resin composition according to claim 1 or 2, wherein (A) Ingredients: (A-2) Acid-modified epoxy (meth)acrylate resin other than the component (A-1).
7. The resin composition according to claim 1 or 2, wherein (A) Weighted average S of the dissolution rate [nm / sec] of the component in the alkaline solution based on the mass ratio (A) Satisfies the following formula (I): 5≤S (A) ≤110···(I)。 8 . The resin composition according to claim 1 , which is a resin composition for forming a solder resist layer of a printed wiring board.
9. A photosensitive film, wherein: A resin composition comprising the resin composition according to any one of claims 1 to 8.
10. A photosensitive film with a support, wherein: The present invention comprises a support body and a resin composition layer provided on the support body and comprising the resin composition according to any one of claims 1 to 8.
11. A printed wiring board, wherein: An insulating layer comprising a cured product of the resin composition according to any one of claims 1 to 8.
12. A semiconductor device, wherein: A printed wiring board as claimed in claim 11.
Citation Information
Patent Citations
Photosensitive element, solder resist and printed wiring board using photosensitive resin composition
JP2014115672A